18.2%-efficient ternary all-polymer organic solar cells with improved stability enabled by a chlorinated guest polymer acceptor - Sun, Rui; Wang, Tao; Fan, Qunping; Wu, Mingjian; Yang, Xinrong; Wu, Xiaohei; Yu, Yue; Xia, Xinxin; Cui, Fengzhe; Wan, Ji; Lu, Xinhui; Hao, Xiaotao; et al. (Joule, 2023)
Although the polymer/polymer blend systems still lag far behind small-molecule-acceptor-based counterparts in power conversion efficiencies (PCEs), the ternary blending strategy provides a simple and promising avenue to achieve an ideal nanoscale blend morphology for reducing the efficiency-stability gap of all-polymer solar cells (all-PSCs). Herein, we designed a narrow-band-gap chlorinated polymer acceptor PY-2Cl and incorporated into the PM6:PY-1S1Se host blend. The addition of PY-2Cl extends the absorption spectra, improves the molecular packing of host-guest acceptors, solidifies the blend microstructure, and suppresses the non-radiative recombination. Consequently, the PCE of the ternary blend is improved up to 18.2% (certified value 17.8%), which represents the highest PCE reported for all-PSCs so far. Impressively, the ternary blend exhibited smaller Urbach energy and better operation stability than did the corresponding binary systems. This work heralds a brighter future for accelerating the development of high-performance all-polymer systems by molecular design and ternary strategy.
CRIS-Team Scopus Importer:2023-01-27
Keywords: all-polymer organic solar cells; high performance; light-soaking stability; polymer acceptor; ternary strategy

2D Metal–Organic Framework Nanosheets based on Pd-TCPP as Photocatalysts for Highly Improved Hydrogen Evolution - Kim, Ji Hyeon; Wu, Siming; Zdrazil, Lukas; Denisov, Nikita; Schmuki, Patrik (Angewandte Chemie International Edition, 2024)
In this report, a 2D MOF nanosheet derived Pd single-atom catalyst, denoted as Pd-MOF, was fabricated and examined for visible light photocatalytic hydrogen evolution reaction (HER). This Pd-MOF can provide a remarkable photocatalytic activity (a H2 production rate of 21.3 mmol/gh in the visible range), which outperforms recently reported Pt-MOFs (with a H2 production rate of 6.6 mmol/gh) with a similar noble metal loading. Notably, this high efficiency of Pd-MOF is not due to different chemical environment of the metal center, nor by changes in the spectral light absorption. The higher performance of the Pd-MOF in comparison to the analogue Pt-MOF is attributed to the longer lifetime of the photogenerated electron-hole pairs and higher charge transfer efficiency.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Metal–Organic Frameworks; Pd Single Atom; Photocatalysis

3D analysis of equally X-ray attenuating mineralogical phases utilizing a correlative tomographic workflow across multiple length scales - Englisch, Silvan; Ditscherlein, Ralf; Kirstein, Tom; Hansen, Leonard; Furat, Orkun; Drobek, Dominik; Leißner, Thomas; Apeleo Zubiri, Benjamin; Weber, Alfred P.; Schmidt, Volker; Peuker, Urs A.; Spiecker, Erdmann (Powder Technology, 2023)
A correlative 3D characterization workflow by micro and nano X-ray computed tomography (Micro-CT, Nano-CT) and analytical scanning electron microscopy (SEM) is presented over different length scales for particle composite materials that apply to any powder at the size scale between 0.3 µm to 15 µm. In this case study, an artificial compound of calcite, talcum, dolomite, and magnesite providing constituent particles with similar morphology, size distribution, and chemical composition for multidimensional separation processes is analyzed. First, Micro-CT characterizes the particle morphology and distribution of a larger amalgamated volume. Then, a smaller, site-specifically prepared pillar is imaged by Nano-CT allowing for correlative investigations at higher-resolution. Afterwards, the Nano-CT reconstruction is informed slice-wise by analytical SEM distinguishing particles with different chemical composition. The statistical interpretation of our results is improved by advanced post-processing and multidimensional analysis, allowing for quantitative characterization of the particles’ size, phase distribution, and mineral degree of liberation.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Correlative 3D analysis; Multidimensional particle characterization; Multiscale X-ray tomography; Parametric copula; Statistical image analysis

A Carbon-Stabilized Austenitic Steel with Lower Hydrogen Embrittlement Susceptibility - Khanchandani, Heena; Zeiler, Stefan; Strobel, Lucas; Göken, Mathias; Felfer, Peter (Steel Research International, 2023)
High-strength steels are susceptible to H-induced failure, which is typically caused by the presence of diffusible H in the microstructure. The diffusivity of H in austenitic steels with face-centered cubic (fcc) crystal structure is slow. The austenitic steels are hence preferred for applications in the hydrogen-containing atmospheres. However, the fcc structure of austenitic steels is often stabilized by the addition of Ni, Mn, or N, which are relatively expensive alloying elements to use. Austenite can kinetically also be stabilized using C. Herein, an approach is applied to a commercial cold work tool steel, where C is used to fully stabilize the fcc phase. This results in a microstructure consisting of only austenite and M7C3 carbide. An exposure to H by cathodic hydrogen charging exhibits no significant influence on the strength and ductility of the C-stabilized austenitic steel. While this material is only a prototype based on an existing alloy of different purposes, it shows the potential for low-cost H-resistant steels based on C-stabilized austenite.
CRIS-Team Scopus Importer:2023-11-03
Keywords: atom probe tomography; austenite stabilizations; diffusible hydrogen; electron backscatter diffractions; hydrogen embrittlements

Activation of Osmium by the Surface Effects of Hydrogenated TiO2 Nanotube Arrays for Enhanced Hydrogen Evolution Reaction Performance - Krstajić Pajić, Mila N.; Dobrota, Ana S.; Mazare, Anca Valentina; Đurđić, Slađana; Hwang, Imgon; Skorodumova, Natalia V.; Manojlović, Dragan; Vasilić, Rastko; Pašti, Igor A.; Schmuki, Patrik; Lačnjevac, Uroš (ACS Applied Materials and Interfaces, 2023)
Efficient cathodes for the hydrogen evolution reaction (HER) in acidic water electrolysis rely on the use of expensive platinum group metals (PGMs). However, to achieve economically viable operation, both the content of PGMs must be reduced and their intrinsically strong H adsorption mitigated. Herein, we show that the surface effects of hydrogenated TiO2 nanotube (TNT) arrays can make osmium, a so far less-explored PGM, a highly active HER electrocatalyst. These defect-rich TiO2 nanostructures provide an interactive scaffold for the galvanic deposition of Os particles with modulated adsorption properties. Through systematic investigations, we identify the synthesis conditions (OsCl3 concentration/temperature/reaction time) that yield a progressive improvement in Os deposition rate and mass loading, thereby decreasing the HER overpotential. At the same time, the Os particles deposited by this procedure remain mainly sub-nanometric and entirely cover the inner tube walls. An optimally balanced Os@TNT composite prepared at 3 mM/55 °C/30 min exhibits a record low overpotential (η) of 61 mV at a current density of 100 mA cm-2, a high mass activity of 20.8 A mgOs-1 at 80 mV, and a stable performance in an acidic medium. Density functional theory calculations indicate the existence of strong interactions between the hydrogenated TiO2 surface and small Os clusters, which may weaken the Os-H* binding strength and thus boost the intrinsic HER activity of Os centers. The results presented in this study offer new directions for the fabrication of cost-effective PGM-based catalysts and a better understanding of the synergistic electronic interactions at the PGM|TiO2 interface.
CRIS-Team Scopus Importer:2023-07-21
Keywords: density functional theory; galvanic deposition; mass activity; metal-support interactions; platinum group metals

Advanced Polycrystalline γ′-Strengthened CoNiCr-Based Superalloys - Neumeier, Steffen; Freund, Lisa; Bezold, Andreas; Köbrich, Manuel; Vollhüter, Jan; Hausmann, D.; Solis, C.; Stark, A.; Schell, N.; Pyczak, F.; Felfer, Peter; Gilles, R.; et al. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
Novel compositionally complex CoNiCr-based superalloys with excellent mechanical properties have been developed, which combine the multiprincipal element nature of high-entropy alloys with the precipitation strengthening in superalloys. A series of advanced polycrystalline γ′-strengthened CoNiCr-based superalloys, called CoWAlloys, with varying contents of Al, W, Ti, Ta, Mo, and Nb are investigated in terms of microstructure, thermophysical properties, yield, and creep strength. The microstructure of all CoWAlloys consists of an fcc solid solution matrix phase (approximate γ composition in at. pct: 50Co–20Ni–20Cr–10X (X = other alloying elements)), which is strengthened by a multicomponent γ′ (Ni,Co)3(Al,Ti,Ta,W,Nb)-based precipitate phase with a very high-volume fraction of around 60 vol pct (approximate γ′ composition in at. pct: 45Ni–30Co–25X). These alloys have high solidus temperatures above 1300 °C and moderate γ′ solvus temperature between 985 °C and 1080 °C leading to a large processing window. The increasing content of γ′-forming elements Ti, Ta, W, and Nb decreases this window, but increases the γ/γ′ lattice misfit and the anti-phase boundary energy, which contribute to a significantly higher yield and creep strength. Their properties are discussed in comparison with conventional polycrystalline Ni-base superalloys and so-called L12-strengthened high-entropy alloys, revealing that the creep strengths of the CoWAlloys are significantly higher. This is due to the reduced strain rate sensitivity of the CoWAlloys due to different underlying deformation mechanisms: By increasing the anti-phase boundary energy, a transition to stacking fault shearing and microtwinning occurs, which leads to the enhanced creep strength. Based on these results, guidelines and strategies for the design of next-generation advanced high-temperature polycrystalline superalloys are proposed. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-03-15

AgIn5S8/ZnS Quantum Dots for Luminescent Down-Shifting and Anti-Reflective Layer in Enhancing Photovoltaic Performance - Kong, Mengqin; Osvet, Andres; Barabash, Anastasia; Zhang, Kaicheng; Hu, Huiying; Elia, Jack; Erban, Christof; Yokosawa, Tadahiro; Spiecker, Erdmann; Batentschuk, Miroslaw; Brabec, Christoph (ACS Applied Materials and Interfaces, 2023)

A Modular and Automated Serial Section Collection System for Ultramicrotomy and Subsequent Imaging - Böhm, Thomas; Felfer, Peter; Thiele, Simon (Microscopy and Microanalysis, 2023)
Ultramicrotomy with automated section collection enables a reliable collection of sequential sections for 3D imaging. Here, we introduce a system for collecting several hundred ultra-thin sections on tape as a flexible polymeric substrate. The tape is stored within a portable cassette, which can be used as a modular platform for different applications. The motorized cassette with its retractable section collection cantilever is installed in front of an ultramicrotome for section collection. Section collection and imaging of the sections can be conducted without requiring any manual handling of the tape, which reduces the risk of specimen contamination and offers various options for automatization and cross-compatibility. For instance, processing steps such as a plasma glow-discharge of the substrate can be performed on the tape while it is enclosed in the cassette. As a proof of concept, more than 300 sequential sections at a thickness of 150 nm were cut from a polymer blend sample and collected on a metal-coated tape. Finally, a subset of 15 × 15 × 15 µm3 of the original sample volume was successfully imaged by confocal Raman microscopy and reconstructed at submicron resolution. The serial section cassette harbors the potential to standardize, simplify, and automate sample library collection, imaging, and storage.
CRIS-Team Scopus Importer:2023-12-29
Keywords: imaging; Raman microscopy; serial sectioning; tomography; ultramicrotomy

Analysis of Strain and Defects in Tellurium-WSe2 Moiré Heterostructures Using Scanning Nanodiffraction - Sari, Bengisu; Zeltmann, Steven E.; Zhao, Chunsong; Pelz, Philipp; Javey, Ali; Minor, Andrew M.; Ophus, Colin; Scott, Mary C. (ACS nano, 2023)
In recent years, there has been an increasing focus on 2D nongraphene materials that range from insulators to semiconductors to metals. As a single-elemental van der Waals semiconductor, tellurium (Te) has captivating anisotropic physical properties. Recent work demonstrated growth of ultrathin Te on WSe2 with the atomic chains of Te aligned with the armchair directions of the substrate using physical vapor deposition (PVD). In this system, a moiré superlattice is formed where micrometer-scale Te flakes sit on top of the continuous WSe2 film. Here, we determined the precise orientation of the Te flakes with respect to the substrate and detailed structure of the resulting moiré lattice by combining electron microscopy with image simulations. We directly visualized the moiré lattice using center of mass-differential phase contrast (CoM-DPC). We also investigated the local strain within the Te/WSe2 layered materials using scanning nanodiffraction techniques. There is a significant tensile strain at the edges of flakes along the direction perpendicular to the Te chain direction, which is an indication of the preferred orientation for the growth of Te on WSe2. In addition, we observed local strain relaxation regions within the Te film, specifically attributed to misfit dislocations, which we characterize as having a screw-like nature. The detailed structural analysis gives insight into the growth mechanisms and strain relaxation in this moiré heterostructure.
CRIS-Team Scopus Importer:2023-12-08
Keywords: defects; moiré superlattices; scanning nanodiffraction; strain; tellurium; WSe

A Sustainable Method for Removal of the Full Range of Liquid and Solid Hydrocarbons from Water Including Up- and Recycling - Gaß, Henrik; Sarcletti, Marco; Müller, Lukas; Hübner, Sabine; Yokosawa, Tadahiro; Park, Hyoungwon; Przybilla, Thomas; Spiecker, Erdmann; Halik, Marcus (Advanced Science, 2023)
Beyond their CO2 emittance when burned as fuels, hydrocarbons (HCs) serve as omnipresent raw materials and commodities. No matter if as liquid oil spills or the endless amounts of plastic roaming the oceans, HCs behave as persistent pollutants with water as main carrier to distribute. Even if their general chemical structure [-(CH2)n-] is quite simple, the endless range of n leads to contaminations of different appearances and properties. A water remediation method based on superparamagnetic iron oxide nanoparticles (SPIONs) modified with self-assembled monolayers of alkyl phosphonic acid derivatives is presented. These molecules enable the SPIONs to non-covalently bind HCs, independently from the molecular weight, size and morphology. The attractive interaction is mainly based on hydrophobic and Coulomb interaction, which allows recycling of the SPIONs. The superparamagnetic core allows a simple magnetic collection and separation from the water phase which makes it a promising addition to wastewater treatment. Agglomerates of collected plastic “waste” even exhibit superior adsorption properties for crude oil, another hydrocarbon waste which gives these collected wastes a second life. This upcycling approach combined with presented recycling methods enables a complete recycling loop.<br

Atomically resolved TEM imaging of covalently functionalised graphene - Dolle, Christian; Schweizer, Peter; Dasler, Daniela; Gsänger, Sebastian; Maidl, Robert; Abellán, Gonzalo; Hauke, Frank; Meyer, Bernd; Hirsch, Andreas; Spiecker, Erdmann (npj 2D Materials and Applications, 2022)
Covalent functionalisation can be a powerful lever to tune the properties and processability of graphene. After overcoming the low chemical reactivity of graphene, covalent functionalisation led to the generation of new hybrid materials, applicable in a broad variation of fields. Although the process of functionalising graphene is nowadays firmly established, fundamental aspects of the produced hybrid materials remain to be clarified. Especially the atomically resolved imaging is only scarcely explored. Here we show aberration corrected in situ high resolution TEM imaging of dodecyl functionalised monolayer graphene at atomic resolution after an effective mechanical filtering approach. The mechanical filtering allows to separate adsorbed contamination from the covalently bound functional molecules and thus opens the possibility for the observation of this hybrid material. The obtained data is validated by DFT calculations and by a novel image simulation approach based on molecular dynamics (MD) simulations at room temperature.
CRIS-Team WoS Importer:2022-05-13

Atomic diffusion in liquid gallium and gallium-nickel alloys probed by quasielastic neutron scattering and molecular dynamic simulations - Shahzad, Anjum; Yang, Fan; Steffen, Julien; Neiß, Christian; Panchenko, Artem; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Embs, Jan Peter; Petry, Winfried; Lohstroh, Wiebke; Görling, Andreas; et al. (Journal of Physics: Condensed Matter, 2024)
The atomic mobility in liquid pure gallium and a gallium-nickel alloy with 2 at% of nickel is studied experimentally by incoherent quasielastic neutron scattering. The integral diffusion coefficients for all-atom diffusion are derived from the experimental data at different temperatures. DFT-based ab-initio molecular dynamics (MD) is used to find numerically the diffusion coefficient of liquid gallium at different temperatures, and numerical theory results well agree with the experimental findings at temperatures below 500 K. Machine learning force fields derived from ab-initio molecular dynamics (AIMD) overestimate within a small 6% error the diffusion coefficient of pure gallium within the genuine AIMD. However, they better agree with experiment for pure gallium and enable the numerical finding of the diffusion coefficient of nickel in the considered melted alloy along with the diffusion coefficient of gallium and integral diffusion coefficient, that agrees with the corresponding experimental values within the error bars. The temperature dependence of the gallium diffusion coefficient D Ga ( T ) follows the Arrhenius law experimentally for all studied temperatures and below 500 K also in the numerical simulations. However, D Ga ( T ) can be well described alternatively by an Einstein-Stokes dependence with the metallic liquid viscosity following the Arrhenius law, especially for the MD simulation results at all studied temperatures. Moreover, a novel variant of the excess entropy scaling theory rationalized our findings for gallium diffusion. Obtained values of the Arrhenius activation energies are profoundly different in the competing theoretical descriptions, which is explained by different temperature-dependent prefactors in the corresponding theories. The diffusion coefficient of gallium is significantly reduced (at the same temperature) in a melted alloy with natural nickel, even at a tiny 2 at% concentration of nickel, as compared with its pure gallium value. This highly surprising behavior contradicts the existing excess entropy scaling theories and opens a venue for further research.
CRIS-Team Scopus Importer:2024-02-16
Keywords: ab-initio molecular dynamics; DFT-based machine learning force fields; gallium-nickel alloy; liquid gallium; quasielastic neutron scattering; self-diffusion

Atomistic simulations of diffusion in γ′ -strengthened Co-based superalloys and its connection to selective alumina formation in early-stage oxidation - Qin, Lin; Kubacka, Dorota; Spiecker, Erdmann; Drautz, Ralf; Rogal, Jutta (Physical Review Materials, 2023)
The suppressed diffusion of Al in γ′ precipitates of Co-based superalloys is suspected to be one of the reasons for the selective formation of alumina during the early-stage oxidation above 900°C. In order to scrutinize this assumption, the diffusion properties of Al, Co, and W in a prototype structure of the γ′ phase, L12-Co3(Al,W), are investigated in a combined density functional theory (DFT) and kinetic Monte Carlo (KMC) study. A particular challenge in simulating diffusion in this ordered phase is the representation and evaluation of numerous migration pathways on the L12 sublattices. With specified diffusion models for the L12 structure and random solid solution (γ phase), our KMC results reveal that Al diffusivity in the γ phase with the same stoichiometric composition is more than two orders of magnitude higher than in the L12 ordered γ′ phase at 900°C. Furthermore, in our rapid thermal exposure experiments for a model Co-based superalloy, the formation of alumina nuclei is observed preferentially in the γ channels while the Al content is comparable in both channels and precipitates before oxidation. Combining these insights from experiment and simulation, the sluggish diffusion of Al in γ′ appears to be a key factor in the selective formation of alumina observed in these systems.
CRIS-Team Scopus Importer:2023-02-17

Between defects and inclusions: The fate of tellurium in pyrite - Börner, Frederik; Keith, Manuel; Fougerouse, Denis; Macauley, Chandra; Felfer, Peter; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann (Chemical Geology, 2023)
Tellurium (Te) is a critical commodity, essential for renewable energy technologies and other high-tech applications. Most Te is currently recovered from anode slimes, i.e., waste arising from copper refining. Rising demand and the key role for the green transition make the diversification and extension of the Te supply important. However, the nature of Te incorporation into ores is still poorly understood and hinders their economic potential. Here, we investigate the distribution of Te in pyrite from a high-grade Au-Ag-Te epithermal-type ore, where pyrite is already processed for ‘invisible’ Au, to inform metallurgical extraction methods, and secure future Te supply. Current models of Te incorporation into pyrite suggest a solid-solution limit in relation to As, similar as for ‘invisible’ Au. In this study, we identified three distinct modes of Te incorporation in pyrite, which challenge previous solubility models: (1) Te solid-solution, at concentrations (up to 285 ppma) that significantly exceed the previously suggested solubility limit. (2) Nano-telluride inclusions along cracks that formed by intra-grain remobilization. (3) Crystal defects, enriched in Te through pipe diffusion hosting up to 0.5 at. % Te. Our results therefore provide new fundamental insights into the chemical and structural coordination of Te in pyrite, which may guide future efforts for its direct recovery.<br
Keywords: Pyrite; Tellurium (Te); Atom probe tomography (APT); Low sulfidation epithermal; Solid solution; Inclusions; Defects; Vatukoula

Breakdown of Magic Numbers in Spherical Confinement - Wang, Junwei; Martín González, Jonathan; Römling, Lukas; Englisch, Silvan; Mbah Chrameh, Fru; Bommineni, Praveen Kumar; Spiecker, Erdmann; Engel, Michael; Vogel, Nicolas (ACS nano, 2025)
Magic numbers in finite particle systems correspond to specific system sizes that allow configurations with low free energy, often exhibiting closed surface shells to maximize the number of nearest neighbors. Since their discovery in atomic nuclei, magic numbers have been essential for understanding the number-structure-property relationships in finite clusters across different scales. However, as the system size increases, the significance of magic numbers diminishes, and the precise system size at which magic number phenomena disappear remains uncertain. In this study, we investigate colloidal clusters formed through confined self-assembly. Small magic number clusters display icosahedral symmetry with closed surface shells, corresponding to pronounced free energy minima. Our findings reveal that beyond a critical system size, closed surface shells disappear, and free energy minima become less pronounced. Instead, we observe a distinct type of colloidal cluster, termed a football cluster, which retains icosahedral symmetry but features lower-coordinated facets disconnected by terraces. A sphere packing model demonstrates that forming closed surface shells becomes impossible beyond a critical system size, explaining the breakdown of magic numbers in large confined systems.
CRIS-Team Scopus Importer:2025-03-28
Keywords: clusters; colloids; confinement; self-assembly; thermodynamics

Bridging theory and experiment in defect-tolerant semiconductors for photovoltaics - Hammer, Maria; Schlott, Hannah; Lüer, Larry; Brabec, Christoph; Sytnyk, Mykhailo; Will, Johannes; Meyer, Bernd; Heiß, Wolfgang (Nature Reviews Materials, 2025)
Defect tolerance is a concept applied in photovoltaics to explain semiconductors such as lead-halide perovskites that excel without relying on single-crystalline growth. It differentiates from the mere absence of defects, emphasizing on minimizing the influence of defects on minority carrier lifetimes. Whether defect tolerance is the only reason for the superiority of lead-halide-perovskite-based solution-processed solar cells is still controversial. However, the defect tolerance of various semiconductor structures and materials has been experimentally suggested and, in some cases, proven. In this Perspective, we explore defect tolerance across material science, defect characterization and computational modelling. With a primary focus on electrically or optically active defects, we systematically compare computational and experimental results from the literature. We aim to address the complexity arising from diverse theoretical approaches that have yielded partially contradictory results. Additionally, experimental findings have been subject to varied interpretations, ranging from defect signals to ion migration. We endeavour to chart a course through this intricacy and seek to establish a rigorous framework for the identification and quantitative assessment of defect toleranc

Catalyst Supraparticles: Tuning the Structure of Spray-Dried Pt/SiO2 Supraparticles via Salt-Based Colloidal Manipulation to Control their Catalytic Performance - Groppe, Philipp; Reichstein, Jakob; Carl, Simon; Cuadrado Collados, Carlos; Niebuur, Bart Jan; Zhang, Kailun; Apeleo Zubiri, Benjamin; Libuda, Jörg; Kraus, Tobias; Retzer, Tanja; Thommes, Matthias; Spiecker, Erdmann; et al. (Small, 2024)
The structure of supraparticles (SPs) is a key parameter for achieving advanced functionalities arising from the combination of different nanoparticle (NP) types in one hierarchical entity. However, whenever a droplet-assisted forced assembly approach is used, e.g., spray-drying, the achievable structure is limited by the inherent drying phenomena of the method. In particular, mixed NP dispersions of differently sized colloids are heavily affected by segregation during the assembly. Herein, the influence of the colloidal arrangement of Pt and SiO2 NPs within a single supraparticulate entity is investigated. A salt-based electrostatic manipulation approach of the utilized NPs is proposed to customize the structure of spray-dried Pt/SiO2 SPs. By this, size-dependent separation phenomena of NPs during solvent evaporation, that limit the catalytic performance in the reduction of 4-nitrophenol, are overcome by achieving even Pt NP distribution. Additionally, the textural properties (pore size and distribution) of the SiO2 pore framework are altered to improve the mass transfer within the material leading to increased catalytic activity. The suggested strategy demonstrates a powerful, material-independent, and universally applicable approach to deliberately customize the structure and functionality of multi-component SP systems. This opens up new ways of colloidal material combinations and structural designs in droplet-assisted forced assembly approaches like spray-drying.
CRIS-Team Scopus Importer:2024-05-10
Keywords: catalysis; porosity; spray-drying; structure control; supraparticles

Characterization of extended defects in 2D materials using aperture-based dark-field STEM in SEM - Denninger, Peter; Schweizer, Peter; Spiecker, Erdmann (Micron, 2024)
Quantitative diffraction contrast analysis with defined diffraction vectors is a well-established method in TEM for studying defects in crystalline materials. A comparable transmission technique is however not available in the more widely used SEM platforms. In this work, we transfer the aperture-based dark-field imaging method from the TEM to the SEM, thus enabling quantitative diffraction contrast studies at lower voltages in SEM. This is achieved in STEM mode by inserting a custom-made aperture between the sample and the STEM detector and centering the hole on a desired reflection. To select individual reflections for dark-field imaging, we use our Low Energy Nanodiffraction (LEND) setup [Schweizer et al., Ultramicroscopy 213, 112956 (2020)], which captures transmission diffraction patterns from a fluorescent screen positioned below the sample. The aperture-based dark-field STEM method is particularly useful for studying extended defects in 2D materials, where (i) stronger diffraction at the lower voltages used in SEM is advantageous, but (ii) two-beam conditions cannot be established, making quantitative diffraction contrast analysis with standard bright-field and annular dark-field detectors impossible. We demonstrate the method by studying basal plane dislocations in bilayer graphene, which have attracted considerable research interest due to their exceptional structural and electronic properties. Direct comparison of results obtained on identical dislocations by the established TEM method and by the new aperture-based dark-field STEM method in SEM shows that a reliable Burgers vector analysis is possible by applying the well-known g·b=0 invisibility criterion. We further use the LEND setup to acquire 4D-STEM data and show that the virtual dark-field images match well with those in aperture-based dark-field STEM images for reliable Burgers vector analysis.
CRIS-Team Scopus Importer:2024-08-30
Keywords: 4D-STEM; Burgers vector analysis; Dark-field imaging; Dislocations in bilayer graphene; Extended defects in 2D materials; STEM in SEM

Combined continuous nanoparticle synthesis with chromatographic size classification - Gromotka, Lukas; Biegel, Markus; Damm, Cornelia; Traore, Nabi; Drobek, Dominik; Spiecker, Erdmann; Peukert, Wolfgang (Advanced Powder Technology, 2024)
In this paper, we report a combination of the continuous flow synthesis of gold nanoparticles (AuNPs) with subsequent purification and narrowing of the particle size distribution (PSD) by size-exclusion chromatography (SEC) by adapting the flow rates of synthesis and classification. First, we show scalability of chromatographic classification with respect to column dimension and the absence of irreversible nanoparticle adhesion on the column material. Two different syntheses lead to a large and widely distributed and a small and narrowly distributed AuNP dispersion, which are classified by a semipreparative column. The PSDs of individual fractions are characterized by analytical SEC. The broadly distributed AuNP dispersion was classified into three fractions with distinct PSDs. For the narrowly distributed AuNPs, the separation is almost independent of the mobile phase flow rate: coarse and fine fractions with almost identical PSDs and separation efficiency curves are observed irrespective of the flow rate. Even NP samples with narrow PSDs can be classified into multiple fractions with tailored PSDs while simultaneously removing dissolved impurities from the dispersion. With our study, we demonstrate the potential of a direct combination of continuous NP synthesis with chromatographic classification for the optimization of final PSDs and the simultaneous purification of nanoparticulate dispersions.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Continuous flow synthesis; Gold nanoparticles; Purification; Size classification; Size-exclusion chromatography

Controlled Self-Assembly of Gold Nanotetrahedra into Quasicrystals and Complex Periodic Supracrystals - Wang, Yi; Chen, Jun; Li, Ruipeng; Götz, Alexander; Drobek, Dominik; Przybilla, Thomas; Hübner, Sabine; Pelz, Philipp; Yang, Lin; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Engel, Michael; et al. (Journal of the American Chemical Society, 2023)
The self-assembly of shape-anisotropic nanocrystals into large-scale structures is a versatile and scalable approach to creating multifunctional materials. The tetrahedral geometry is ubiquitous in natural and manmade materials, yet regular tetrahedra present a formidable challenge in understanding their self-assembly behavior as they do not tile space. Here, we report diverse supracrystals from gold nanotetrahedra including the quasicrystal (QC) and the dimer packing predicted more than a decade ago and hitherto unknown phases. We solve the complex three-dimensional (3D) structure of the QC by a combination of electron microscopy, tomography, and synchrotron X-ray scattering. Nanotetrahedron vertex sharpness, surface ligands, and assembly conditions work in concert to regulate supracrystal structure. We also discover that the surface curvature of supracrystals can induce structural changes of the QC tiling and eventually, for small supracrystals with high curvature, stabilize a hexagonal approximant. Our findings bridge the gap between computational design and experimental realization of soft matter assemblies and demonstrate the importance of accurate control over nanocrystal attributes and the assembly conditions to realize increasingly complex nanopolyhedron supracrystals.
CRIS-Team Scopus Importer:2023-09-29

Determination of 2D Particle Size Distributions in Plasmonic Nanoparticle Colloids via Analytical Ultracentrifugation: Application to Gold Bipyramids. - Frank, Uwe; Drobek, Dominik; Sánchez-Iglesias, Ana; Wawra, Simon; Nees, Nico; Walter, Johannes; Pflug, Lukas; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Liz-Marzan, Luis M.; Peukert, Wolfgang (ACS nano, 2023)
Multidimensional particle properties determine the product properties in numerous advanced applications. Accurate and statistically meaningful measurements of complex particles and their multidimensional distributions are highly challenging but strongly needed. 2D particle size distributions of plasmonic nanoparticles of complex regular shape can be obtained from analytical ultracentrifugation experiments via the optical back coupling method. A workflow for the calculation of frictional properties of arbitrarily shaped nanoparticles was developed based on bead shell models and applied to gold bipyramids with a pentagonal cross-section. The obtained 2D particle length-diameter distributions and the reduced cumulative 1D length and diameter distributions were compared to transmission electron microscopy measurements. While we find very good agreement for most measurements, the obtained length and diameter distributions were shifted by a few nanometers for some samples. Transmission electron microscopy, energy-dispersive X-ray spectroscopy, electron tomography, and finite element modeling indicate that the shift originated from a slight mismatch between the assumed shape of the simulated perfect bipyramids and the real particle shape and composition due to the presence of silver in the particles. This study demonstrates the feasibility of the applied techniques for complex shape analysis of nanoparticle ensembles with unmatched particle count numbers.
Keywords: analytical ultracentrifugation; bead modeling; electron tomography; extinction cross section; gold bipyramids; optical back coupling; particle shape distribution

Dewetting of Pt Nanoparticles Boosts Electrocatalytic Hydrogen Evolution Due to Electronic Metal-Support Interaction - Harsha, Shreyas; Sharma, Rakesh K.; Dierner, Martin; Baeumer, Christoph; Makhotkin, Igor; Mul, Guido; Ghigna, Paolo; Spiecker, Erdmann; Will, Johannes; Altomare, Marco (Advanced Functional Materials, 2024)
Solid-state dewetting is the heat-induced agglomeration of thin metal films into defined nanoparticles (NPs). Dewetted Pt nanoparticles are investigated on F-doped SnO2 (FTO) substrates as model binder-free electrodes for the hydrogen evolution reaction (HER). Dewetting of Pt films into particles exposes the FTO substrate and the metal/support (Pt-FTO) contact line. Despite the decrease in Pt electrochemical surface area (ECSA) upon dewetting, dewetted NPs show a >3-fold increase in ECSA-normalized HER activity compared to as-deposited nanocrystalline Pt films. Electrodes designed with dewetted Pt NPs of different sizes show that the HER activity does not only correlate with the ECSA but also increases with increasing the Pt-FTO contact line length. The smaller the NPs, the larger the Pt-FTO contact line, and the higher the activity. This effect is ascribed to electronic metal-support interaction (EMSI), due to electron transfer from FTO to Pt. It is proposed that EMSI effects alter the electronic structure of Pt sites near the Pt-FTO contact line, facilitating the H2 evolution kinetics. When NPs are a few nm-sized, a large mass fraction of Pt is affected by EMSI, resulting in a further increase of HER activity compared to NPs ≥10 nm despite the lower ECSA.
CRIS-Team Scopus Importer:2024-08-23
Keywords: electrocatalysis; electronic metal-support interaction; hydrogen evolution reaction; nanoparticles; platinum; solid-state dewetting

Dry reforming of methane over gallium-based supported catalytically active liquid metal solutions - Wolf, Moritz; de Oliveira, Ana; Taccardi, Nicola; Maisel, Sven; Heller, Martina; Khan Antara, Sharmin; Soegaard, Alexander; Felfer, Peter; Görling, Andreas; Haumann, Marco; Wasserscheid, Peter (Communications Chemistry, 2023)
Gallium-rich supported catalytically active liquid metal solutions (SCALMS) were recently introduced as a new way towards heterogeneous single atom catalysis. SCALMS were demonstrated to exhibit a certain resistance against coking during the dehydrogenation of alkanes using Ga-rich alloys of noble metals. Here, the conceptual catalytic application of SCALMS in dry reforming of methane (DRM) is tested with non-noble metal (Co, Cu, Fe, Ni) atoms in the gallium-rich liquid alloy. This study introduces SCALMS to high-temperature applications and an oxidative reaction environment. Most catalysts were shown to undergo severe oxidation during DRM, while Ga-Ni SCALMS retained a certain level of activity. This observation is explained by a kinetically controlled redox process, namely oxidation to gallium oxide species and re-reduction via H2 activation over Ni. Consequentially, this redox process can be shifted to the metallic side when using increasing concentrations of Ni in Ga, which strongly suppresses coke formation. Density-functional theory (DFT) based ab initio molecular dynamics (AIMD) simulations were performed to confirm the increased availability of Ni at the liquid alloy-gas interface. However, leaching of gallium via the formation of volatile oxidic species during the hypothesised redox cycles was identified indicating a critical instability of Ga-Ni SCALMS for prolonged test durations.
CRIS-Team Scopus Importer:2023-10-27

Early-stage bifurcation of crystallization in a sphere - Mbah, Chrameh Fru; Wang, Junwei; Englisch, Silvan; Bommineni, Praveen Kumar; Varela Rosales, Nydia; Spiecker, Erdmann; Vogel, Nicolas; Engel, Michael (Nature Communications, 2023)
Bifurcations in kinetic pathways decide the evolution of a system. An example is crystallization, in which the thermodynamically stable polymorph may not form due to kinetic hindrance. Here, we use confined self-assembly to investigate the interplay of thermodynamics and kinetics in the crystallization pathways of finite clusters. We report the observation of decahedral clusters from colloidal particles in emulsion droplets and show that these decahedral clusters can be thermodynamically stable, just like icosahedral clusters. Our hard sphere simulations reveal how the development of the early nucleus shape passes through a bifurcation that decides the cluster symmetry. A geometric argument explains why decahedral clusters are kinetically hindered and why icosahedral clusters can be dominant even if they are not in the thermodynamic ground state.
CRIS-Team Scopus Importer:2023-09-08

Efficient, stable, and fully printed carbon-electrode perovskite solar cells enabled by hole-transporting bilayers - Du, Tian; Qiu, Shudi; Zhou, Xin; Le Corre, Vincent Marc; Wu, Mingjian; Dong, Lirong; Peng, Zijian; Zhao, Yicheng; Jang, Dongju; Spiecker, Erdmann; Brabec, Christoph; Egelhaaf, Hans-Joachim (Joule, 2023)
Printable planar carbon electrodes emerge as a promising replacement for thermally evaporated metals as the rear contact for perovskite solar cells (PSCs). However, the power conversion efficiencies (PCEs) of the state-of-the-art carbon-electrode PSC (c-PSC) noticeably lag behind their metal-electrode counterparts. Here, we propose a hole-transporting bilayer (HTbL) configuration to improve the fill factor and the open-circuit voltage of c-PSCs simultaneously. The HTbL is prepared by sequentially blade coating two organic semiconductors between perovskite and carbon, with the outer HTL enhancing hole extraction to carbon, while the inner HTL mitigates perovskite surface recombination. Consequently, our fully printed c-PSCs with HTbL outperform those with single HTL, and a stabilized champion PCE of 19.2% is achieved compared with that of 17.3%. Our prototype c-PSC stably operates during 1 sun, 65°C aging test (ISOS-L-2I) for 2,500 h showing negligible PCE drop, validating its potential as a highly cost-effective photovoltaic technology.
CRIS-Team Scopus Importer:2023-08-18
Keywords: bilayer; carbon electrode; fully printed perovskite solar cells; hole transporting; stability

Enhanced Photostability of Lead Halide Perovskite Nanocrystals with Mn3+ Incorporation - Hu, Huiying; Fehn, Dominik; Barr, Maissa; Harreiß, Christina; Zhao, Yicheng; Meyer, Karsten; Osvet, Andres; Brabec, Christoph (ACS Applied Materials and Interfaces, 2024)
Recently, lead halide perovskite nanocrystals (NCs) have shown great potential and have been widely studied in lighting and optoelectronic fields. However, the long-term stability of perovskite NCs under irradiation is an important challenge for their application in practice. Mn2+ dopants are mostly proposed as substitutes for the Pb site in perovskite NCs synthesized through the hot-injection method, with the aim of improving both photo- and thermal stability. In this work, we employed a facile ligand-assisted reprecipitate strategy to introduce Mn ions into perovskite lattice, and the results showed that Mn3+ instead of Mn2+, even with a very low level of incorporation of 0.18 mol % as interstitial dopant, can enhance the photostability of perovskite binder film under the ambient conditions without emission change, and the photoluminescent efficiency can retain 70% and be stable under intensive irradiation for 12 h. Besides, Mn3+ incorporation could prolong the photoluminescent decay time by passivating trap defects and modifying the distortion of the lattice, which underscores the significant potential for application as light emitters.
CRIS-Team Scopus Importer:2024-05-17
Keywords: interstitial doping; passivation; perovskite nanocrystal; photoluminescence; photostability

Exploring the Preparation Dependence of Crystalline 2D-Extended Ultrathin C8-BTBT-C8 Films - Hawly, Tim; Johnson, Manuel; Späth, Andreas; Nickles Jäkel, Hannah; Wu, Mingjian; Spiecker, Erdmann; Watts, Benjamin; Nefedov, Alexei; Fink, Rainer (ACS Applied Materials and Interfaces, 2022)
Crystalline organic semiconducting thin films from the benchmark molecule C8-BTBT-C8 were obtained using physical vapor deposition and various solution-based methods. Utilizing atomic force microscopy and X-ray spectromicroscopy, we illustrate the influence of the underlying growth mechanism and determine the highly preparation-dependent orientation of the thiophene backbone. We observe a continuous trend for crystalline C8-BTBT-C8 thin film domains to extend into the square millimeter-range under near-equilibrium growth conditions. For such well-defined systems, electron diffraction tomography allows us to precisely determine the unit cell directly after film deposition and to reveal an 8° molecular tilt angle with respect to the surface normal. This finding is in almost perfect accordance with the values derived from near-edge X-ray absorption fine structure linear dichroism. Within this work, we shine a light on both the successes and challenges connected to the realization of potent, thiophene-based semiconducting films, paving the way toward square centimeter-sized ultrathin organic crystals and their application in organic circuitry.
CRIS-Team Scopus Importer:2022-04-22
Keywords: 2D nanomaterials; electron tomography; molecular self-assembly; organic semiconductors; organic thin films; X-ray microspectroscopy

Fast Gas-Adsorption Kinetics in Supraparticle-Based MOF Packings with Hierarchical Porosity - Fujiwara, Atsushi; Wang, Junwei; Hiraide, Shotaro; Götz, Alexander; Miyahara, Minoru T.; Hartmann, Martin; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Vogel, Nicolas; Watanabe, Satoshi (Advanced Materials, 2023)
Metal–organic frameworks (MOFs) are microporous adsorbents for high-throughput gas separation. Such materials exhibit distinct adsorption characteristics owing to the flexibility of the crystal framework in a nanoparticle, which can be different from its bulk crystal. However, for practical applications, such particles need to be compacted into macroscopic pellets, creating mass-transport limitations. In this work, this problem is addressed by forming materials with structural hierarchy, using a supraparticle-based approach. Spherical supraparticles composed of nanosized MOF particles are fabricated by emulsion templating and they are used as the structural component forming a macroscopic material. Zeolitic imidazolate framework-8 (ZIF-8) particles are used as a model system and the gas-adsorption kinetics of the hierarchical material are compared with conventional pellets without structural hierarchy. It is demonstrated that a pellet packed with supraparticles exhibits a 30 times faster adsorption rate compared to an unstructured ZIF-8 powder pellet. These results underline the importance of controlling structural hierarchy to maximize the performance of existing materials. In the hierarchical MOFs, large macropores between the supraparticles, smaller macropores between individual ZIF-8 primary particles, and micropores inherent to the ZIF-8 framework collude to combine large surface area, defined adsorption sites, and efficient mass transport to enhance performance.
CRIS-Team Scopus Importer:2023-10-06
Keywords: adsorption kinetics; hierarchical porosity; metal–organic frameworks; self-assembly; supraparticles

From Meso to Macro: Controlling Hierarchical Porosity in Supraparticle Powders - Sultan, Umair; Götz, Alexander; Schlumberger, Carola; Drobek, Dominik; Bleyer, Gudrun; Walter, Teresa; Loewer, Erik; Peuker, Urs Alexander; Thommes, Matthias; Spiecker, Erdmann; Apeleo Zubiri, Benjamin; Inayat, Alexandra; et al. (Small, 2023)
A drying droplet containing colloidal particles can consolidate into a spherical assembly called a supraparticle. Such supraparticles are inherently porous due to the spaces between the constituent primary particles. Here, the emergent, hierarchical porosity in spray-dried supraparticles is tailored via three distinct strategies acting at different length scales. First, mesopores (<10 nm) are introduced via the primary particles. Second, the interstitial pores are tuned from the meso- (35 nm) to the macro scale (250 nm) by controlling the primary particle size. Third, defined macropores (>100 nm) are introduced via templating polymer particles, which can be selectively removed by calcination. Combining all three strategies creates hierarchical supraparticles with fully tailored pore size distributions. Moreover, another level of the hierarchy is added by fabricating supra-supraparticles, using the supraparticles themselves as building blocks, which provide additional pores with micrometer dimensions. The interconnectivity of the pore networks within all supraparticle types is investigated via detailed textural and tomographic analysis. This work provides a versatile toolbox for designing porous materials with precisely tunable, hierarchical porosity from the meso- (3 nm) to the macroscale (≈10 µm) that can be utilized for applications in catalysis, chromatography, or adsorption.
CRIS-Team Scopus Importer:2023-04-07
Keywords: adsorption; hierarchy; porous materials; self-assembly; supraparticles; tomography

Gram-Scale Continuous Flow Synthesis of Silver-on-Silica Patchy Nanoparticles with Widely Tunable Resonances for Plasmonics Applications - Völkl, Andreas; Toutouly, Jannick; Drobek, Dominik; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Klupp Taylor, Robin (ACS Applied Nano Materials, 2023)
Extensive research has been conducted on colloids that incorporate nanostructured noble metals, motivated in particular by their highly tunable optical properties. However, the lack of approaches that offer reproducibility, tunability and scalable production is limiting their exploitation in many application areas. Here we present an innovative process for the controlled formation of silver patches on silica nanospheres using gold nanocrystal seeds. The synthesis of the seeds and their attachment in very small numbers to the silica spheres is achieved without employing any surfactants, stabilizers or linker molecules. Using advanced transmission electron microscopy techniques, we show that electroless deposition of nanostructured silver occurs at the introduced seeds and leads to a central protrusion from the metal patches not observed in earlier, seed-free work. We demonstrate both seeding and growth processes can be achieved in millimixer flow reactors. With this simple and scalable approach we provide compelling evidence for the use of seeds in producing targeted morphology and function. Specifically, patch size and optical properties can be tailored in a predictive manner by adjusting the density of seeds on the silica nanospheres as well as reagent concentrations during growth. As a result, our process can be used to obtain colloidal dispersions with localized surface plasmon resonance peaks anywhere in the range 400 nm to nearly 1300 nm. We confirm the scalability of our method by operating the growth process for around 70 minutes. Apart from changes in the first few minutes, the product properties remained rather stable and over a gram of high quality silver patch coated silica could be recovered. Our approach opens up exciting new avenues for plasmonics applications which typically require large amounts of nanoparticles with specifically designed optical properties. These include color and IR pigments, photocatalysts, and as light management components in optoelectronic devices like photovoltaic cells.<br
Keywords: Patchy particles; continuous flow synthesis; continuous flow; static T-mixer; seeded growth; gold nanoparticles; silver patches; interface engineering; localized surface plasmon resonance; scale-up

Grätzel-Type TiO2 Anatase Layers as Host for Pt Single Atoms: Highly Efficient and Stable Photocatalytic Hydrogen Production - Kerketta, Ujjaval; Kim, Hyesung; Denisov, Nikita; Schmuki, Patrik (Advanced Energy Materials, 2023)
Single atoms (SAs) represent not only a new frontier in classic heterogeneous catalysis but are also increasingly investigated as co-catalysts in photocatalytic reactions. In contrast to classic catalysis, many photocatalytic platforms require only a very low SA loading density to reach a saturated photocatalytic activity. As a result, an optimized light harvesting/carrier transport combination in the supporting semiconductor becomes the key aspect for the overall photocatalytic efficiency. In this work, it is demonstrated that Grätzel type mesoporous TiO2 layers represent an ideal host for Pt single-atoms (SAs) that allow for a highly effective photocatalytic H2 generation. Using a layer with an optimized geometry, structure, as well as Pt SA loading, a photocatalytic H2 production is achieved of up to ≈2900 µL h−1 (under irradiation at λ = 365 nm and I = 65 mW cm−2) – a performance that is far superior to previous Pt SA/TiO2 structures based on TiO2 nanotubes, nanosheets, or metal organic frameworks. Moreover, such SA/substrate combination provides a highly stable H2 production over time. The present work thus introduces the use of this classic TiO2 nanostructure as the most effective host for Pt SAs and its use for highly efficient photocatalytic H2 production from aqueous solutions.
CRIS-Team Scopus Importer:2023-12-08
Keywords: mesoporous titanium dioxide; photocatalytic hydrogen production; Pt single atoms

Hexagonal Hybrid Bismuthene by Molecular Interface Engineering - Dolle, Christian; Oestreicher, Victor; Ruiz, Alberto M.; Kohring, Malte; Garnes-Portolés, Francisco; Wu, Mingjian; Sánchez-Santolino, Gabriel; Seijas-Da Silva, Alvaro; Alcaraz, Marta; Eggeler, Yolita M.; Spiecker, Erdmann; Canet-Ferrer, Josep; et al. (Journal of the American Chemical Society, 2023)
High-quality devices based on layered heterostructures are typically built from materials obtained by complex solid-state physical approaches or laborious mechanical exfoliation and transfer. Meanwhile, wet-chemically synthesized materials commonly suffer from surface residuals and intrinsic defects. Here, we synthesize using an unprecedented colloidal photocatalyzed, one-pot redox reaction a few-layers bismuth hybrid of “electronic grade” structural quality. Intriguingly, the material presents a sulfur-alkyl-functionalized reconstructed surface that prevents it from oxidation and leads to a tuned electronic structure that results from the altered arrangement of the surface. The metallic behavior of the hybrid is supported by ab initio predictions and room temperature transport measurements of individual nanoflakes. Our findings indicate how surface reconstructions in two-dimensional (2D) systems can promote unexpected properties that can pave the way to new functionalities and devices. Moreover, this scalable synthetic process opens new avenues for applications in plasmonics or electronic (and spintronic) device fabrication. Beyond electronics, this 2D hybrid material may be of interest in organic catalysis, biomedicine, or energy storage and conversion.<br

Highly Localized Optical Field Enhancement at Neon Ion Sputtered Tungsten Nanotips - Paschen, Timo; Brückner, Leon; Wu, Mingjian; Spiecker, Erdmann; Hommelhoff, Peter (Nano Letters, 2023)
We present laser-driven rescattering of electrons at a nanometric protrusion (nanotip), which is fabricated with an in situ neon ion sputtering technique applied to a tungsten needle tip. Electron energy spectra obtained before and after the sputtering show rescattering features, such as a plateau and high-energy cutoff. Extracting the optical near-field enhancement in both cases, we observe a strong increase of more than 2-fold for the nanotip. Accompanying finite-difference time-domain (FDTD) simulations show a good match with the experimentally extracted near-field strengths. Additionally, high electric field localization for the nanotip is found. The combination of transmission electron microscope imaging of such nanotips and the determination of the near-field enhancement by electron rescattering represent a full characterization of the electric near-field of these intriguing electron emitters. Ultimately, nanotips as small as single nanometers can be produced, which is of utmost interest for electron diffraction experiments and low-emittance electron sources.<br

Highly Ordered Monolayers of μm-Sized Polystyrene Spheres Studied by Grazing-Incidence Small-Angle X-ray Scattering, Simulations, and Geometrical Calculations - Maiti, Santanu; Senavirathna, L. N.; Minguez Bacho, Ignacio; Menath, Johannes; Gruber, W.; Vogel, Nicolas; Bachmann, Julien; Unruh, Tobias (Langmuir, 2024)
Unraveling the two-dimensional (2D) structural ordering of colloidal particles assembled at a flat surface is essential for understanding and optimizing their physical properties. So far, grazing-incidence small-angle X-ray scattering (GISAXS) has been widely used to determine crystallographic information on 2D self-assembled structures of nanosize objects. However, solving the structure of 2D lattices consisting of micrometer (μm)-sized objects still remains a challenge using scattering methods. Here, a model 2D SCALMS (supported catalytically active liquid metal solution) template is fabricated from μm-sized polystyrene (PS) spheres that form a monolayer on top of the flat solid support. GISAXS patterns of the sample were collected for rotation angles around its surface normal in steps of 3°. For every rotation angle, different Bragg-type interference maxima along the out-of-plane (qz) direction were observed. On the basis of simulations of GISXAS patterns of single domains of ordered particle arrangements using the distorted wave Born approximation (DWBA) and validation against a simple geometrical scattering model, the interference maxima could nicely be interpreted to originate from a monolayer of the μm-sized spherical particles which are arranged in domains of hexagonal 2D paracrystalline order. This novel GISAXS evaluation technique serves as a proof of principle for determining the μm-size periodicity of 2D crystalline domains and demonstrates its potential to spatially resolve the relative orientations of such domains with respect to a reference direction.
CRIS-Team Scopus Importer:2024-02-09

Highly Stable Lasing from Solution-Epitaxially Grown Formamidinium-Lead-Bromide Micro-Resonators - Afify, Hany A.; Sytnyk, Mykhailo; Rehm, Viktor; Barabash, Anastasia; Mashkov, Oleksandr; Osvet, Andres; Volobuev, Valentine V.; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Götz, Klaus; Unruh, Tobias; et al. (Advanced Optical Materials, 2022)
High-quality epitaxial growth of oriented microcrystallites on a semiconductor substrate is demonstrated here for formamidinium lead bromide perovskite, by drop casting of precursor solutions in air. The microcrystallites exhibit green photoluminescence at room temperature, as well as lasing with low thresholds. Lasing is observed even though the substrate is fully opaque at the lasing wavelengths, and even though it has a higher refractive index as the perovskite active material. Moreover, the lasing is stable for more than 109 excitation pulses, which is more than what is previously achieved for devices kept in the air. Such highly stable lasing under pulsed excitation represents an important step towards continuous mode operation or even electrical excitation in future perovskite-based devices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: halide perovskites; lasing; microresonators; solution epitaxy

High temperature oxidation resistance of physical vapor deposited Hf-Si-B-2 +/- z thin films - Glechner, T.; Bahr, A.; Hahn, R.; Wojcik, T.; Heller, Martina; Kirnbauer, A.; Ramm, J.; Kolozsvari, S.; Felfer, Peter; Riedl, H. (Corrosion Science, 2022)
Within physical vapor deposited Hf-Si-B-2 +/- z thin films, selective diffusion-driven oxidation of Si is identified to cause outstanding oxidation resistance at temperatures up to 1500 degrees C. After 60 h at 1200 degrees C, the initially 2.47 mu m thin Hf0.20Si0.23B0.57 thin film exhibits a dense oxide scale of only 1.56 mu m. The thermally induced decomposition of metastable Hf-Si-B-2 +/- z leads not only to the formation of Si precipitates within the remaining thin film (related to a non-homogenous Si distribution after the deposition) but also to pure Si layers on top and bottom of the Hf-Si-B-2 +/- z coatings next to the excellent adherend SiO2 based scales.
CRIS-Team WoS Importer:2022-07-15

Impact of 2D Ligands on Lattice Strain and Energy Losses in Narrow-Bandgap Lead–Tin Perovskite Solar Cells - Zhang, Kaicheng; Vincze, Andrej; Metwalli, Ezzeldin; Zhang, Jiyun; Liu, Chao; Meng, Wei; Zhang, Boxue; Tian, Jingjing; Heumüller, Thomas; Xie, Zhiqiang; Luo, Junsheng; Osvet, Andres; et al. (Advanced Functional Materials, 2023)
Mixed lead and tin (Pb/Sn) hybrid perovskites exhibit a great potential in fabricating all-perovskite tandem devices due to their easily tunable bandgaps. However, the energy deficit and instability in Pb/Sn perovskite solar cells (PSCs) constrain their practical applications, which renders defect passivation engineering indispensable to develop highly efficient and long-term stable PSCs. Herein, the mechanisms of strain tailoring and defect passivation in Pb/Sn PSCs by 2D ligands are investigated. The 2D ligands include electroneutral cations with long alkyl chain (LAC), iodates with relatively short alkyl chain (SAC) and their mixtures. This study reveals that LAC ligands facilitate the relaxation of tensile strain in perovskite films while SAC ligands cause strain buildup. By mixing LAC/SAC ligands, tensile strain in perovskite films can be balanced which improves solar cell performance. PSCs with admixed β-guanidinopropionic acid (GUA)/phenethylammonium iodide (PEAI) exhibit enhanced open circuit voltage and fill factor, which is attributed to reduced nonradiative recombination losses in the bulk and at the interfaces. Furthermore, the operational stability of PSCs is slightly improved by the mixed 2D ligands. This work reveals the mechanisms of 2D ligands in strain tailoring and defect passivation toward efficient and stable narrow-bandgap PSCs.
CRIS-Team Scopus Importer:2023-07-07
Keywords: 2D ligand passivation; energy losses; lead/tin perovskite solar cells; stability; strain tailoring

Increasing Activity of Trimetallic Oxygen Reduction PtNiMo/C Catalysts Through Initial Conditioning - Danisman, Bilal; Zhang, Gui Rong; Baumunk, Adrian F.; Yang, Juntao; Brummel, Olaf; Darge, Philipp; Dworschak, Dominik; Mayrhofer, Karl J.J.; Libuda, Jörg; Zhou, Xin; Wu, Mingjian; Spiecker, Erdmann; et al. (ChemElectroChem, 2024)
This study investigates the importance of preconditioning in Pt-alloy catalysts for oxygen–reduction reactions. Previous research indicated that slower scanning rates during preconditioning initially boost activity, but this is followed by a rapid decline. The study reveals the required number of cycles to achieve the first constant steady state activity in PtNiMo/C catalysts when using slower scanning rates during preconditioning. It also highlights the resulting activity differences. Remarkably, a catalyst preconditioned with 150 slow cycles showed an activity of approximately 1.25 mA cm−2 at 0.90 VRHE, significantly higher than one preconditioned at a fast rate (0.82 mA cm−2). Both ex–situ and in–situ analyses revealed that Pt, along with Ni, was leached during pretreatment. At slower scan rates of 20 mV s−1, the dissolved Pt redeposited as highly active, small-sized clusters or single atoms. Fast scan rates of of 500 mV s−1, in contrast, resulted in fewer such clusters. Accelerated stress tests up to 1.10 VRHE confirmed the high stability of these clusters, demonstrating a substantial activity increase even after 24,000 cycles.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Accelerated Durability; Cyclic Voltammetry; Nanoparticles; Oxygen Reduction; Pretreatment

Influence of Au alloying on solid state dewetting kinetics and texture evolution of Ag and Ni thin films - Dierner, Martin; Will, Johannes; Landes, Michael; Volland, Christian; Branscheid, Robert; Zech, Tobias; Unruh, Tobias; Spiecker, Erdmann (Surfaces and Interfaces, 2024)
In this contribution, the effect of Au alloying on the solid state dewetting (SSD) kinetics and texture evolution of AuNi and AuAg thin films is investigated. For that bilayers of a high (AuNi) and low (AuAg) atomic mismatch system are fabricated on different substrates and annealed utilizing a rapid thermal annealing furnace. Afterwards, the degree of SSD, as well as the texturing, are investigated by correlating X-ray diffraction and electron microscopy techniques. A quantitative texture analysis yields that pure metal films (Ni, Au, Ag) exhibit the same degree of 〈111〉 texturing after SSD. In contrast, a reduced degree of texturing is observed for alloys as well as for pure Ni films on amorphous substrates. The texture loss is less pronounced for AuNi on sapphire which is likely due to in-plane texturing along densely packed directions stabilizing the 〈111〉 out-of-plane texture. Further the effect of alloying on the SSD kinetics is investigated. We found that the SSD kinetics of the low-misfit AuAg system continuously changes with the Au concentration and can be perfectly described by composition dependent hole growth as reflected by the Mullins’ coefficient. In contrast, the high-misfit AuNi system resembles this behaviour only during early stages of SSD. For prolonged annealing times at 850 °C as well as 890 °C a strong deviation is observed, which in particular manifests in the concentration range from 50 at% to 70 at% Au, where a drastic increase in the dewetting rate is observed. The deviation from the Mullins coefficient indicates a shift in the prevailing mechanism, suggesting that this accelerated SSD occurs at compositions where the annealing temperature (T) approaches the melting temperature (Tm), i.e. liquidus line. Indeed, the reduced temperature (T/Tm) exhibits its maximum within the compositional range where accelerated SSD is prominent. Additionally, Au segregation at grain boundaries, an increase in surface anisotropy, and a decrease in surface energy are discussed as stabilizing factors for low and high Au concentrations, respectively.<br
Keywords: Solid state dewetting; Binary alloys; Texture evolution; TEM; XRD; Thermodynamics

Influence of substrate polarity on thermal stability, grain growth and atomic interface structure of Au thin films on ZnO surfaces - Dierner, Martin; Landes, Michael; Will, Johannes; Ziegler, Andreas; Hübner, Sabine; Przybilla, Thomas; Zech, Tobias; Unruh, Tobias; Meyer, Bernd; Spiecker, Erdmann (Acta Materialia, 2025)
The influence of the polarity of ceramic substrates on the structural evolution of thin metal films during annealing at elevated temperatures is investigated, including the competing processes of solid state dewetting (SSD) and grain growth, as well as the atomic structure of the epitaxial interface. For this purpose, Au thin films on polar O-ZnO(0001‾) and Zn-ZnO(0001) surfaces are annealed at elevated temperatures and times. Whereas SSD dominates on the O-terminated surface, pronounced grain growth is observed on the Zn-terminated surface. The texture analysis revealed that up to 600 °C, both samples exhibit a fiber texture with slightly dominating Au(111)[110] || ZnO(0001)[112¯0] orientation relation (OR 2). At 800 °C, Au on Zn-ZnO exhibits a transformation to a mazed bicrystal structure with Au(111)[110] || ZnO(0001)[101¯0] orientation relation (OR 1). Comparison of various interface structures in density-functional theory (DFT) indicates that atomically sharp interfaces between the Au(111) films and the ideal bulk-truncated polar ZnO surfaces are energetically favored for both substrate polarities in excellent agreement with atomically resolved electron microscopy. Due to the larger period of the coincidence site lattice in OR 2, the corresponding interface can be described as semi-coherent with clearly separated misfit dislocations. In contrast, the much smaller period of the (approximate) coincidence site lattice in OR 1 leads to a largely incoherent interface with local reconstructions. However, in the experimental situation, even a small rotational deviation from the perfect OR 1 can introduce an interfacial screw dislocation network superimposed on the incoherent interface structure, effectively making the interface semi-coherent.
CRIS-Team Scopus Importer:2025-01-31
Keywords: DFT; Electron microscopy; Grain growth; iDPC; Interfaces; Solid-state dewetting; Texture

Influence of tin oxide decoration on the junction conductivity of silver nanowires - Vogl, Lilian; Kalancha, Violetta; Schweizer, Peter; Denninger, Peter; Wu, Mingjian; Brabec, Christoph; Forberich, Karen; Spiecker, Erdmann (Nanotechnology, 2023)
Flexible electrodes using nanowires (NWs) suffer from challenges of long-term stability and high junction resistance which limit their fields of applications. Welding via thermal annealing is a common strategy to enhance the conductivity of percolated NW networks, however, it affects the structural and mechanical integrity of the NWs. In this study we show that the decoration of NWs with an ultrathin metal oxide is a potential alternative procedure which not only enhances the thermal and chemical stability but, moreover, provides a totally different mechanism to reduce the junction resistance upon heat treatment. Here, we analyze the effect of SnO x decoration on the conductance of silver NWs and NW junctions by using a four-probe measurement setup inside a scanning electron microscope. Dedicated transmission electron microscopy analysis in plan-view and cross-section geometry are carried out to characterize the nanowires and the microstructure of the junctions. Upon heat treatment the junction resistance of both plain silver NWs and SnO x -decorated NWs is reduced by around 80%. While plain silver NWs show characteristic junction welding during annealing, the SnO x -decoration reduces junction resistance by a solder-like process which does not affect the mechanical integrity of the NW junction and is therefore expected to be superior for applications.
CRIS-Team Scopus Importer:2023-02-24
Keywords: electrical measurements; electron microscopy; junctions; nanowires

Isolated Rh atoms in dehydrogenation catalysis - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Tacardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Isolated active sites have great potential to be highly efficient and stable in heterogeneous catalysis, while enabling low costs due to the low transition metal content. Herein, we present results on the synthesis, first catalytic trials, and characterization of the Ga9Rh2 phase and the hitherto not-studied Ga3Rh phase. We used XRD and TEM for structural characterization, and with XPS, EDX we accessed the chemical composition and electronic structure of the intermetallic compounds. In combination with catalytic tests of these phases in the challenging propane dehydrogenation and by DFT calculations, we obtain a comprehensive picture of these novel catalyst materials. Their specific crystallographic structure leads to isolated Rhodium sites, which is proposed to be the decisive factor for the catalytic properties of the systems.
CRIS-Team Scopus Importer:2023-03-31

Levitating the future: light, magnet, and fiber unite - Chakraborty, Soumya; Wong, Gordon Kwan Leung; Oda, Ferdi; Wachter, Vanessa; Kusminskiy, Silvia Viola; Yokosawa, Tadahiro; Hübner, Sabine; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Distaso, Monica; Russell, Philip St. J.; Joly, Nicolas (Proceedings Volume PC12991, Nanophotonics X, 2024)
We report the first-ever observation of optomagnetically-driven rotation of a magnetic particle, optically levitated inside a chiral hollow-core photonic crystal fibre (HC-PCF). Rotation of the optically biaxial particle causes a change in the transmitted power and ellipticity of a linearly polarised probe beam at 632.8 nm. HC-PCF offers a versatile platform for investigating the optomechanical response of levitated magnetic particle

Light‐induced agglomeration of single‐atom platinum in photocatalysis - Denisov, Nikita; Qin, Shanshan; Will, Johannes; Vasiljevic, Bojana Nedić; Skorodumova, Natalia V.; Pašti, Igor A.; Sarma, Bidyut Bikash; Osuagwu, Benedict; Yokosawa, Tadahiro; Voß, Johannes; Wirth, Janis; Spiecker, Erdmann; et al. (Advanced Materials, 2022)
With recent advances in the field of single-atoms (SAs) used in photocatalysis, an unprecedented performance of atomically dispersed co-catalysts has been achieved. However, the stability and agglomeration of SA co-catalysts on the semiconductor surface may represent a critical issue in potential applications. Here we describe the photoinduced destabilization of Pt SAs on the benchmark photocatalyst, TiO2. In aqueous solutions within illumination timescales ranging from few minutes to several hours, light-induced agglomeration of Pt SAs to ensembles (dimers, multimers) and finally nanoparticles takes place. The kinetics critically depends on the presence of sacrificial hole scavengers and the used light intensity. DFT calculations attribute the light induced destabilization of the SA Pt species to binding of surface-coordinated Pt with solution-hydrogen (adsorbed H atoms), which consequently weakens the Pt SA bonding to the TiO2 surface. Despite the gradual aggregation of Pt SAs into surface clusters and their overall reduction to metallic state, which involves >90% of Pt SAs, the overall photocatalytic H2 evolution remains virtually unaffected.<br

Loading of CAR‐T cells with magnetic nanoparticles for controlled targeting suppresses inflammatory cytokine release and switches tumor cell death mechanism - Pfister, Felix; Carnell, Lucas; Löffler, Lisa; Boosz, Philipp; Schaft, Niels; Dörrie, Jan; Stein, René; Lenz, Malte; Spiecker, Erdmann; Huber, Christian; Haddadin, Sami; Berking, Carola; et al. (MedComm, 2025)
Therapies against hematological malignancies using chimeric antigen receptors (CAR)-T cells have shown great potential; however, therapeutic success in solid tumors has been constrained due to limited tumor trafficking and infiltration, as well as the scarcity of cancer-specific solid tumor antigens. Therefore, the enrichment of tumor-antigen specific CAR-T cells in the desired region is critical for improving therapy efficacy and reducing systemic on-target/off-tumor side effects. Here, we functionalized human CAR-T cells with superparamagnetic iron oxide nanoparticles (SPIONs), making them magnetically controllable for site-directed targeting. SPION-loaded CAR-T cells maintained their specific cytolytic capacity against melanoma cells expressing the CAR-specific antigen chondroitin sulfate proteoglycan (CSPG4). Importantly, SPIONs suppressed cytokine release in the loaded CAR-T cells, shifting the cell death phenotype in the tumor cells from pyroptosis to apoptosis. Furthermore, SPION-loaded CAR-T cells could be enriched in a dynamic flow model through an external magnetic field and be detected in MRI. These results demonstrate that lytic cytotoxicity is retained after SPION-functionalization and provides a basis for future site-specific immunotherapies against solid tumors with reduced systemic adverse side effect

Localized phase transformation strengthening in CoNi-based superalloys - Bezold, Andreas; Egan, Ashton; Völkl, Julian; Karpstein, Nicolas; Gaag, Tobias; Spiecker, Erdmann; Göken, Mathias; Mills, Michael J.; Neumeier, Steffen (Scripta Materialia, 2025)
Segregation processes during high-temperature deformation can be either detrimental or beneficial in γ′-strengthened superalloys depending on which elements segregate. In intermediate CoNi-based superalloys only softening due to extensive microtwinning was observed so far. By analyzing the creep behavior of a Ta-free and a Ta-containing CoNi-based superalloy at 750 °C and 620 MPa, we show that strengthening segregation behaviors along various planar defects, including microtwinning, can be achieved in this alloy class. While both alloys deformed under planar fault formation, the Ta-containing alloy outperformed the Ta-free alloy. Atomic-scale energy dispersive spectroscopy investigations revealed strengthening effects by local phase transformations along superlattice intrinsic and extrinsic stacking faults in both alloys. However, microtwinning is enhanced in the Ta-free alloy, while it is impeded in the Ta-containing alloy. Given the faster diffusivity of Ta compared to W, kinetic effects on localized phase transformation strengthening and their subsequent influence on the creep behavior are discussed.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Creep; Segregation; Stacking fault; Superalloy; Transmission electron microscopy

Magnetic in situ determination of surface coordination motifs by utilizing the degree of particle agglomeration - Wolf, Andreas; Zink, Andreas; Stiegler, Lisa; Branscheid, Robert; Apeleo Zubiri, Benjamin; Müssig, Stephan; Peukert, Wolfgang; Walter, Johannes; Spiecker, Erdmann; Mandel, Karl (Journal of Colloid and Interface Science, 2023)
Most analytical techniques used to study the surface chemical properties of superparamagnetic iron oxide nanoparticles (SPIONs) are barely suitable for in situ investigations in liquids, where SPIONs are mostly applied for hyperthermia therapy, diagnostic biosensing, magnetic particle imaging or water purification. Magnetic particle spectroscopy (MPS) can resolve changes in magnetic interactions of SPIONs within seconds at ambient conditions. Herein, we show that by adding mono- and divalent cations to citric acid capped SPIONs, the degree of agglomeration can be utilized to study the selectivity of cations towards surface coordination motifs via MPS. A favored chelate agent, like ethylenediaminetetraacetic acid (EDTA) for divalent cations, removes cations from coordination sites on the SPION surface and causes redispersion of agglomerates. The magnetic determination thereof represents what we call a “magnetically indicated complexometric titration”. The relevance of agglomerate sizes for the MPS signal response is studied on a model system of SPIONs and the surfactant cetrimonium bromide (CTAB). Analytical ultracentrifugation (AUC) and cryogenic transmission electron microscopy (cryo-TEM) reveal that large micron-sized agglomerates are required to significantly change the MPS signal response. With this work, a fast and easy-to-use characterization method to determine surface coordination motifs of magnetic nanoparticles in optically dense media is demonstrated.
Keywords: Superparamagnetic iron oxide nanoparticles (SPIONs); Magnetic particle spectroscopy (MPS); Agglomeration; Colloidal surface chemistry; Cation coordination

Mechanistic insights into silver-gold nanoalloy formation by two-dimensional population balance modeling - Traore, Nabi; Schikarski, Tobias; Cardenas Lopez, Paola Ivonne; Körner, A.; Cardenas Lopez, Paola Ivonne; Hartmann, Lukas; Fritsch, B.; Walter, Johannes; Hutzler, A.; Pflug, Lukas; Peukert, Wolfgang (Chemical Engineering Journal, 2024)
The large-scale synthesis of nanoparticles (NPs) with defined properties requires detailed understanding of the underlying formation mechanisms and kinetics. The formation mechanisms of bimetallic NPs are still not sufficiently understood due to the complex reaction chemistry, which makes the control of the supersaturation as the thermodynamic driving force challenging. Particle size, chemical composition, and the distribution of the elements within the particles change dynamically during particle formation. In this work, we propose a mechanism for the formation of bimetallic silver-gold alloy NPs via a green liquid-phase co-reduction synthesis and develop a two-dimensional population balance model to quantitatively describe the evolution of particle size distribution, composition, and optical properties. We shed light on the complex multi-stage formation mechanism of a highly relevant bimetallic NP system, lay the foundation for tailoring the process conditions to achieve targeted optical particle properties and unravel predictive property-process relationships.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Alloy Nanoparticle; Formation Mechanism; Gold Nanoparticle; Nanoparticle Synthesis; Population Balance Equation; Silver Nanoparticle

Mesoscopic Structure of Lipid Nanoparticle Formulations for mRNA Drug Delivery: Comirnaty and Drug-Free Dispersions - Unruh, Tobias; Götz, Klaus; Vogel, Carola; Fröhlich, Erik; Scheurer, Andreas; Porcar, Lionel; Steiniger, Frank (ACS nano, 2024)
Lipid nanoparticles (LNPs) produced by antisolvent precipitation (ASP) are used in formulations for mRNA drug delivery. The mesoscopic structure of such complex multicomponent and polydisperse nanoparticulate systems is most relevant for their drug delivery properties, medical efficiency, shelf life, and possible side effects. However, the knowledge on the structural details of such formulations is very limited. Essentially no such information is publicly available for pharmaceutical dispersions approved by numerous medicine agencies for the use in humans and loaded with mRNA encoding a mimic of the spike protein of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) as, e.g., the Comirnaty formulation (BioNTech/Pfizer). Here, we present a simple preparation method to mimic the Comirnaty drug-free LNPs including a comparison of their structural properties with those of Comirnaty. Strong evidence for the liquid state of the LNPs in both systems is found in contrast to the designation of the LNPs as solid lipid nanoparticles by BioNTech. An exceptionally detailed and reliable structural model for the LNPs i.a. revealing their unexpected narrow size distribution will be presented based on a combined small-angle X-ray scattering and photon correlation spectroscopy (SAXS/PCS) evaluation method. The results from this experimental approach are supported by light microscopy, 1H NMR spectroscopy, Raman spectroscopy, cryogenic electron microscopy (cryoTEM), and simultaneous SAXS/SANS studies. The presented results do not provide direct insights on particle formation or dispersion stability but should contribute significantly to better understanding the LNP drug delivery process, enhancing their medical benefit, and reducing side effects.
CRIS-Team Scopus Importer:2024-04-12
Keywords: BNT162b2 Comirnaty; dynamic light scattering (DLS; lipid nanoparticles (LNPs); mRNA drug delivery; PCS); proton nuclear magnetic resonance spectroscopy (; severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2); small-angle X-ray scattering (SAXS)

Microscopic mechanism of the L12–D019 phase transformation in a Co-base single crystal superalloy - Karpstein, Nicolas; Laplanche, Guillaume; Saksena, Aparna; Zehl, Rico; Bezold, Andreas; Horst, Oliver M.; Bürger, David; Kostka, Aleksander; Zenk, Christopher; Neumeier, Steffen; Gault, Baptiste; Ludwig, Alfred; et al. (Acta Materialia, 2025)
In γ′-strengthened superalloys based on the Co-Al-W system, the stability of the γ′ phase is often limited, as it is found to transform into other phases such as B2 and D019 after long-term annealing. To explore the details behind the annealing-induced transformation from the metastable L12-γ′ phase to the thermodynamically stable D019-χ phase in the single-crystalline Co-base superalloy ERBOCo-VF60 (Co79.8Al8.9W9.0Ta2.3 in at.%), scanning transmission electron microscopy and atom probe tomography are employed. Due to the structural similarity between the L12 and D019 structures, coherent plate-shaped χ precipitates are formed in the γ/γ′ microstructure parallel to 111 planes through a shear-based transformation mechanism. While the χ phase precipitates slowly during isothermal aging, its formation can be significantly accelerated locally by coating the superalloy with a Cr-rich layer, which indirectly stabilizes the χ phase as revealed by thermodynamic calculations. This procedure allowed us to obtain an intermediate (incomplete) state of χ-phase formation in terms of both crystal structure and composition. By characterizing the partial dislocations at the tip of growing χ precipitates, the microscopic details of the shear-based cubic-to-hexagonal transformation from L12 to D019 are uncovered. The compositional aspect of the transformation involves a significant diffusion-mediated enrichment of W in the χ phase, accompanied by a simultaneous W depletion in the γ′ phase, leading to its transformation to the γ phase.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Atom probe tomography; Cobalt-base superalloys; Phase transformations; Stacking faults; Transmission electron microscopy

Miniaturized gas exposure devices for atom probe experiments - Ott, Benedict; Heller, Martina; Monajem, Mehrpad; Felfer, Peter (Microscopy research and technique, 2024)
To detect hydrogen in materials at the atomic scale, atom probe tomography is now regularly used. In order to avoid cumbersome cryo-preparation to suppress diffusion, often hydrogen is charged only into the finished specimen. Here, the use of hydrogen gas over electrochemical hydrogen has the advantage that the specimen is not contaminated with an electrolyte. So far, this “charging” has been done in large, expensive systems. Here, we introduce small devices that enable the exposure of atom probe specimens to hydrogen and potentially other gases, using only very small gas volumes. This enables the operation in regular laboratory environments without additional safety measures. These devices can be used to expose the specimen to hydrogen up to 10 bar/90°C. Higher temperatures may be attained with small changes. Validation of the success of charging with these setups is demonstrated through experiments employing deuterium charging of palladium atom probe tips. Research Highlights: Enabling the exposure of atom probe specimens to hydrogen and potentially other gases, using only very small gas volumes. Built setups can be assembled with little money and from freely available parts, making specimen charging much easier. Validation of the success of charging with these setups is demonstrated through experiments employing deuterium charging of palladium atom probe tips.
CRIS-Team Scopus Importer:2024-05-10
Keywords: atom probe; atom probe tomography; deuterium; deuterium gas charging

Noncovalent Liquid Phase Functionalization of 2H-WS2with PDI: An Energy Conversion Platform with Long-Lived Charge Separation - Scharl, Tobias; Binder, Gerhard; Chen, Xin; Yokosawa, Tadahiro; Cadranel, Alejandro; Knirsch, Kathrin; Spiecker, Erdmann; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
Transition metal dichalcogenides are attractive 2D materials in the context of solar energy conversion. Previous investigations have focused predominantly on the properties of these systems. The realization of noncovalent hybrids with, for example, complementary electroactive materials remains underexplored to this date for exfoliated WS2. In this contribution, we explore WS2 by means of exfoliation and integration together with visible light-absorbing and electron-accepting perylene diimides into versatile electron-donor acceptor hybrids. Important is the distinct electron-donating feature of WS2. Detailed spectroscopic investigations of WS2-PDI confirm the electron donor/acceptor nature of the hybrid and indicate that green light photoexcitation leads to the formation of long-lived WS2+-PDIcharge-separated states.
CRIS-Team Scopus Importer:2022-04-14

Oxide scale microstructure and failure mechanism of alloy 601 under varying metal dusting conditions - Schlereth, C.; Weiser, Martin; White, E.; Felfer, Peter; Galetz, M. (Journal of Materials Science, 2024)
Chemical plants which process highly carbonaceous gases at elevated temperatures are prone to catastrophic corrosion by metal dusting. Typically, commercial alloys with high amounts of protective oxide scale formers (Cr, Al, and Si) are used in these environments. However, scale failure is still frequently observed after an incubation time initiating pits. In this study, the microstructure and subsequent metal dusting-induced failure of the oxide scale on the commercial Ni-based alloy 601 was analyzed. Samples were exposed in different aggressive metal dusting gases and characterized using metallographic cross sections, electron beam microanalysis (EPMA), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and transmission electron microscopy (TEM). A thin and protective chromia scale formed in some regions with a continuous silica layer below. Across most of the alloy 601 surfaces, internal oxidation of Al could be linked to metallic particles in the outer scale. Additionally, MnCr2O4 was observed in the outer scale. Together with pores in the chromia, the spinel and metallic particles in the outer scale combined to provide pathways for carbon ingress. After exposure in a gas with a higher driving force for carbon deposition, a higher amount of carbon was incorporated in the growing oxide scale, resulting in earlier scale failure and metal dusting pit initiation. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2024-01-19

Photocatalytic H2 Generation: Controlled and Optimized Dispersion of Single Atom Co-Catalysts Based on Pt-TCPP Planar Adsorption on TiO2 - Qin, Shanshan; Denisov, Nikita; Kim, Hyesung; Schmuki, Patrik (Angewandte Chemie International Edition, 2024)
When using single atoms (SAs) as a co-catalyst in photocatalytic H2 generation, achieving a well-dispersed, evenly distributed and adjustable SA surface density on a semiconductor surface is a challenging task. In the present work we use the planar adsorption of tetrakis-(4-carboxyphenyl)-porphyrin (TCPP) and its platinum coordinated analogue, Pt-TCPP, onto anatase TiO2 surfaces to establish a spatially controlled decoration of SAs. We show that the surface Pt SA density can be very well controlled by co-adsorption of Pt-TCPP and TCPP in the planar monolayer regime, and by adjusting the Pt-TCPP to TCPP ratio a desired well dispersed surface density of SAs up to 2.6×105 atoms μm−2 can be established (which is the most effective Pt SA loading for photocatalysis). This distribution and the SA state are maintained after a thermal treatment in air, and an optimized SA density as well as a most active form of Pt for photocatalytic H2 evolution can be established and maintained.
CRIS-Team Scopus Importer:2024-02-16
Keywords: hydrogen evolution; photocatalysis; platinum; porphyrins; single-atom catalysts

Photodeposition-Based Synthesis of TiO2@IrOx Core–Shell Catalyst for Proton Exchange Membrane Water Electrolysis with Low Iridium Loading - Hoffmeister, Darius; Finger, Selina; Fiedler, Lena; Ma, Tien Ching; Körner, Andreas; Zlatar, Matej; Fritsch, Birk; Bodnar, Kerstin Witte; Carl, Simon; Götz, Alexander; Zubiri, Benjamin Apeleo; Will, Johannes; et al. (Advanced Science, 2024)
The widespread application of green hydrogen production technologies requires cost reduction of crucial elements. To achieve this, a viable pathway to reduce the iridium loading in proton exchange membrane water electrolysis (PEMWE) is explored. Herein, a scalable synthesis method based on a photodeposition process for a TiO2@IrOx core–shell catalyst with a reduced iridium content as low as 40 wt.% is presented. Using this synthesis method, titania support particles homogeneously coated with a thin iridium oxide shell of only 2.1 ± 0.4 nm are obtained. The catalyst exhibits not only high ex situ activity, but also decent stability compared to commercially available catalysts. Furthermore, the unique core–shell structure provides a threefold increased electrical powder conductivity compared to structures without the shell. In addition, the low iridium content facilitates the fabrication of sufficiently thick catalyst layers at decreased iridium loadings mitigating the impact of crack formation in the catalyst layer during PEMWE operation. It is demonstrated that the novel TiO2@IrOx core–shell catalyst clearly outperforms the commercial reference in single-cell tests with an iridium loading below 0.3 mgIr cm−2 exhibiting a superior iridium-specific power density of 17.9 kW gIr−1 compared to 10.4 kW gIr−1 for the commercial reference.
CRIS-Team Scopus Importer:2024-06-21
Keywords: core–shell catalyst; iridium utilization; low loading; proton exchange membrane water electrolysis; thickness factor

Pitting corrosion-Preferred chloride diffusion pathways in physical vapor deposited AlCrN coatings - Hudak, O. E.; Bahr, A.; Kutrowatz, P.; Wojcik, T.; Bohrn, F.; Solyom, L.; Schuster, R.; Shang, L.; Hunold, O.; Polcik, P.; Heller, Martina; Felfer, Peter; et al. (Corrosion Science, 2023)
Pitting corrosion of sputtered and arc evaportaed fcc-AlCrN coated low-alloy steel substrates was studied in a 0.1 M NaCl solution, using a three-electrode-cell. Depending on the deposition technique, several diffusion mechanisms were identified by high-resolution techniques (i.e. APT, TOF-SIMS). For arc evaporated AlCrN, incoherently embedded macro-particles provided the majority of fast-track diffusion pathways and pit-initiation sites, while their pristine coating matrix proved protective against chloride inward diffusion. Contrarily, the more coarse-grained sputtered AlCrN morphology with a highly orientated crystal growth featured diffusion paths along column boundaries, where chloride permeated the coating structure and initiated pit formations at the coating-substrate interface.
CRIS-Team WoS Importer:2023-01-13

Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
The development of a robust quasi-ohmic contact with minimal resistance, good stability and cost-effectiveness is crucial for perovskite solar cells. We introduce a generic approach featuring a Lewis-acid layer sandwiched between dopant-free semicrystalline polymer and metal electrode in perovskite solar cells, resulting in an ideal quasi-ohmic contact even at elevated temperature up to 85 °C. The solubility of Lewis acid in alcohol facilitates nondestructive solution processing on top of polymer, which boosts hole injection from polymer into metal by two orders of magnitude. By integrating the polymer-acid-metal structure into solar cells, devices exhibit remarkable resilience, retaining 96% ± 3%, 96% ± 2% and 75% ± 7% of their initial efficiencies after continuous operation in nitrogen at 35 °C for 2212 h, 55 °C for 1650 h and 85 °C for 937 h, respectively. Leveraging the Arrhenius relation, we project an impressive T80 lifetime of 26,126 h at 30 °C.
CRIS-Team Scopus Importer:2024-03-15

Polythiophene as a Double-Electrostatic Template for Zinc Oxide and Gold: Multicomponent Nano-Objects for Enhanced Photocatalysis - Bernhardt, Sarah; Yokosawa, Tadahiro; Spiecker, Erdmann; Gröhn, Franziska (Langmuir, 2023)
Using electrostatic self-assembly and electrostatic nanotemplating, a quaternary nanostructured system consisting of zinc oxide nanoparticles, gold nanoparticles, poly[3-(potassium-4-butanoate)thiophene-2,5-diyl] (PT), and methyltrioctylammonium chloride (MTOA) (PT-MTOA-ZnO-Au) was designed for aqueous photocatalysis. The PT-MTOA hollow sphere aggregates served as an electrostatic template for both individual inorganic nanoparticles controlling their morphology, stabilizing the nanoparticles, and acting as a photosensitizer. The hybrid structures included spherical ZnO nanoparticles with a diameter of d = 2.6 nm and spherical Au nanoparticles with d = 6.0 nm embedded in PT-MTOA hollow spheres with a hydrodynamic radius of RH = 100 nm. The ZnO nanoparticles acted as the main catalyst, while the Au nanoparticles acted as the cocatalyst. As a photocatalytic model reaction, the dye degradation of methylene blue in aqueous solution using the full spectral range from UV to visible light was tested. The photocatalytic activity was optimized by varying the Zn and Au loading ratios and was substantially enhanced regarding the components; for example, it was increased by about 61% using PT-MTOA-ZnO-Au compared to the composite without gold particles. A photocatalytic mechanism of the methylene blue degradation was proposed when catalyzed by these multicomponent nano-objects. Thus, a simple procedure of templating two different nanoparticle species within the same cocatalytically active template has been demonstrated, which can be extended to other inorganic particles, making a variety of task-specific catalysts accessible.
CRIS-Team Scopus Importer:2023-08-11

Population balance modeling of InP quantum dots: Experimentally enabled global optimization to identify unknown material parameters - Wang, Zhuang; Traore, Nabi; Schikarski, Tobias; Stiegler, Lisa; Drobek, Dominik; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Walter, Johannes; Peukert, Wolfgang; Pflug, Lukas; Segets, Doris (Chemical Engineering Science, 2023)
Despite great progress in the synthetic chemistry of InP QDs, a predictive model to describe their temporal formation is still missing. In this work, we introduce a population balance model incorporating liquid phase reactions, homogeneous nucleation and reaction-limited growth of InP supported with the highly reproducible and reliable experimental data acquired from an automated robotic synthesis platform. A comparison between experimental kinetic data (different initial concentrations and temperatures) and simulations was made. The proposed model describes the temporal evolution of solid concentration, particle diameter and particle size distribution very well. The quantitative agreement between experiments and simulations was only achieved by global optimization to identify unknown and hardly measurable material parameters and kinetic constants such as surface energy, growth rate constants or activation energies. We see this model rendering the first step towards the development of more refined models that enable rigorous optimization and control of the production process for III-V semiconductors.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Automated synthesis; InP; Population balance equation; Simulation

Porphyrin adsorption and ligand exchange at the (110)-TiO2 / organic liquid interface - Götz, Klaus; Stollberg, Isabella; Prihoda, Annemarie; Bertram, Florian; Metwalli, Ezzeldin; Zech, Tobias; Unruh, Tobias (Surface Science, 2022)
Highly efficient dye-sensitized solar cells (DSSCs) have been prepared on the basis of porphyrin dyes with significant success. Recent studies have demonstrated a correlation between the solar cell efficiency and the configuration of the adsorbed porphyrin molecules at the surface of the semiconducting support material. The preparation of dense self assembled monolayers (SAMs) of upright standing porphyrin molecules on TiO2 surfaces was achieved from toluene solutions only when using a molecular exchange reaction. Here, an exchange study of an oleic acid (OLA) SAM on a <110> TiO2 surface by porphyrin molecules is presented. The exchange reaction has been studied by ex-situ as well as in-situ X-ray reflectometry (XRR) measurements. It was found that an almost complete exchange of OLA with porphyrins can be achieved. With increasing coating times the orientation of the porphyrin molecules relative to the substrate surface changed from flat lying to upright standing.
CRIS-Team Scopus Importer:2022-04-15
Keywords: DESY; functionalization; interface; porphyrin; rutile; X-ray reflectometry

Post-deposition annealing and interfacial atomic layer deposition buffer layers of Sb2Se3/CdS stacks for reduced interface recombination and increased open-circuit voltages - Weiss, Thomas Paul; Minguez-Bacho, Ignacio; Zuccala, Elena; Melchiorre, Michele; Valle, Nathalie; El Adib, Brahime; Yokosawa, Tadahiro; Spiecker, Erdmann; Bachmann, Julien; Dale, Phillip J.; Siebentritt, Susanne (Progress in Photovoltaics, 2022)
Currently, Sb2Se3 thin films receive considerable research interest as a solar cell absorber material. When completed into a device stack, the major bottleneck for further device improvement is the open-circuit voltage, which is the focus of the work presented here. Polycrystalline thin-film Sb2Se3 absorbers and solar cells are prepared in substrate configuration and the dominant recombination path is studied using photoluminescence spectroscopy and temperature-dependent current–voltage characteristics. It is found that a post-deposition annealing after the CdS buffer layer deposition can effectively remove interface recombination since the activation energy of the dominant recombination path becomes equal to the bandgap of the Sb2Se3 absorber. The increased activation energy is accompanied by an increased photoluminescence yield, that is, reduced non-radiative recombination. Finished Sb2Se3 solar cell devices reach open-circuit voltages as high as 485 mV. Contrarily, the short-circuit current density of these devices is limiting the efficiency after the post-deposition annealing. It is shown that atomic layer-deposited intermediate buffer layers such as TiO2 or Sb2S3 can pave the way for overcoming this limitation.
CRIS-Team Scopus Importer:2022-10-14
Keywords: ALD buffer layer; earth abundant; interface recombination; post-deposition annealing; Sb; solar cell; thin film

Preparation of atom probe tips from (nano)particles in dispersion using (di)electrophoresis and electroplating - Vorlaufer, Nora; Josten, Jan; Carl, Simon; Göbel, Erik; Soegaard, Alexander; Taccardi, Nicola; Spiecker, Erdmann; Felfer, Peter (Microscopy Research and Technique, 2023)
The behavior of catalytic particles depends on their chemical structure and morphology. To reveal this information, the characterization with atom probe tomography has huge potential. Despite progresses and papers proposing various approaches towards the incorporation of particles inside atom probe tips, no single approach has been broadly applicable to date. In this paper, we introduce a workflow that allowed us to prepare atom probe specimens from Ga particles in suspension in the size range of 50 nm up to 2 μm. By combining dielectrophoresis and electrodeposition in a suitable way, we achieve a near-tip shape geometry, without a time-consuming FIB lift-out. This workflow is a simple and quick method to prepare atom probe tips and allows for a high preparation throughput. Also, not using a lift-out allowed us to use a cryo-stage, avoiding melting of the Ga particles, while ensuring a mechanical stable atom probe tip. The specimen prepared by this workflow enable a stable measurement and low fracture rates.<br

Pt-single atom decorated TiO2: Tuning anodic TiO2 nanotube structure and geometry toward a high-performance photocatalytic H2 production - Chen, Xuewen; Qin, Shanshan; Denisov, Nikita; Kure-Chu, Song Zhu; Schmuki, Patrik (Electrochimica Acta, 2023)
Atomically dispersed Pt single atoms (SAs) on titania have been reported to be a highly effective co-catalyst in photocatalytic H2 generation. In this report, we grew layers of anodic TiO2 nanotubes (NTs) varying the lengths of the NTs from 1 to 18 μm as well as their crystalline state by thermal annealing over a wide range of temperatures (350 °C – 800 °C). We then decorated the nanotubes with single atom (SA) Pt co-catalysts deposited from H2PtCl6 solutions with various concentrations of 0.001–2 mM Pt and evaluate the photocatalytic H2 generation performance for the different NT layers under UV and solar illumination. The highest photocatalytic performance is achieved for 15–18 μm long anatase NTs decorated with Pt SAs from a 0.01 mM H2PtCl6 solution (leading to a Pt SA surface concentration of 5.6 × 105 /µm2). Except for a sufficient SA Pt loading and an anatase structure, the key parameter is the photon absorption length for near-band-gap UV and AM 1.5 light. Such optimized Pt SA@TiO2 NTs show a most efficient H2, outperforming many other photocatalytic 3D titania structures, such as titania-based powders, flakes, and Metal–Organic Frameworks (MOFs) tested under the same illumination conditions.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Photocatalytic H; Pt single atoms; TiO; TiO; TiO

Pt single atoms dispersed in a hybrid MOFox-in-nanotube structure for efficient and long-term stable photocatalytic H2 generation - Qin, Shanshan; Guo, Junli; Chen, Xuewen; Cao, Ran; Denisov, Nikita; Song, Yan Yan; Schmuki, Patrik (Journal of Materials Chemistry A, 2023)
Atomically dispersed Pt single atoms (SAs) have been reported to be a highly effective co-catalyst on TiO2 for photocatalytic H2 generation. Many TiO2 supports have been explored for hosting Pt SAs. Particularly 1D titania hosts allow for an optimized light and charge carrier management. But, attached Pt SAs often suffer from agglomeration during the photocatalytic process. In this context, titania-based metal-organic frameworks (MOFs), such as MIL-125, have attracted wide attention, as they provide stable anchoring sites for Pt SAs. To combine the beneficial features of the 1D TiO2 morphology with the SA stability, we introduce here a hierarchical structure, where the Pt SAs are dispersed in MOF-derived porous oxide features that are embedded in aligned anodic TiO2 nanotubes. This hybrid structure is intrinsically (within the nanotubes) synthesized and combines the excellent light harvesting and carrier transport properties of titania nanotubes with the beneficial features of MOF. As a result of this synergy, we obtain not only a high photocatalytic H2 evolution efficiency but most importantly a remarkably long-term stability of H2 evolution under UV light (365 nm) or simulated solar light (AM 1.5).
CRIS-Team Scopus Importer:2023-09-15

Pt Single Atoms Loaded on Thin-Layer TiO2 Electrodes: Electrochemical and Photocatalytic Features - Zhou, Xin; Wang, Yue; Denisov, Nikita; Kim, Hyesung; Kim, Ji Hyeon; Will, Johannes; Spiecker, Erdmann; Vaskevich, Alexander; Schmuki, Patrik (Small, 2024)
Recently, the use of Pt in the form of single atoms (SA) has attracted considerable attention to promote the cathodic hydrogen production reaction from water in electrochemical or photocatalytic settings. First, produce suitable electrodes by Pt SA deposition on Direct current (DC)-sputter deposited titania (TiO2) layers on graphene—these electrodes allow to characterization of the electrochemical properties of Pt single atoms and their investigation in high-resolution HAADF-STEM. For Pt SAs loaded on TiO2, electrochemical H2 evolution shows only a very small overpotential. Concurrent with the onset of H2 evolution, agglomeration of the Pt SAs to clusters or nanoparticles (NPs) occurs. Potential cycling can be used to control SA agglomeration to variable-size NPs. The electrochemical activity of the electrode is directly related to the SA surface density (up to reaching the activity level of a plain Pt sheet). In contrast, for photocatalytic H2 generation already a minimum SA density is sufficient to reach control by photogenerated charge carriers. In electrochemical and photocatalytic approaches a typical TOF of ≈100–150 H2 molecules per second per site can be reached. Overall, the work illustrates a straightforward approach for reliable electrochemical and photoelectrochemical investigations of SAs and discusses the extraction of critical electrochemical factors of Pt SAs on titania electrodes.
CRIS-Team Scopus Importer:2024-08-23
Keywords: anatase thin film electrode; electrocatalytic hydrogen evolution; graphene; photocatalytic hydrogen evolution; Pt Single atom

Quantification of the temperature-dependent evolution of defect structures in a CoNi-base superalloy - Bezold, Andreas; Volz, Nicklas; Lenz, Malte; Karpstein, Nicolas; Zenk, Christopher; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Acta Materialia, 2022)
Quantifying the individual contributions of specific deformation mechanisms to the total plastic strain is of primary importance to understand the underlying deformation behavior and assess the significance of the different mechanisms. However, this quantification is nearly impossible in Ni-base superalloys due to the inherent difficulties in determining the propagation distances of the respective shearing dislocations. In this study, the occurrence of stacking faults (SFs) at temperatures between 750 °C and 1000 °C in the single crystalline CoNi-base superalloy ERBOCo-4 provides an opportunity to systematically quantify the evolution of the defect structures as a function of temperature and strain after constant strain-rate compressive tests. The quantification approach revealed that deformation is still localized in the matrix at 750 °C. With increasing temperature, the main deformation mechanism changes to SF shearing, which contributes 74% of the total deformation during the initial yielding stage (∼ 0.3% plastic strain) at 900 °C. Deformation spreads significantly more homogeneously across the γ/γ’ microstructure with increasing plastic strain. Extremely high stacking fault densities and frequent fault interactions cause a pronounced work-hardening anomaly at 850 °C. Structural characterization on the atomic scale confirms the strengthening effect of SFs as barriers to partial dislocation propagation. A strong correlation between the possible diffusion length of segregating solutes and the operant shearing mechanisms reveals the significance of segregation on the occurring deformation mechanisms.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Co-base superalloy; Defect structures; High temperature deformation; Transmission electron microscopy; Yielding behavior

Reactive Deposition Versus Strong Electrostatic Adsorption (SEA): A Key to Highly Active Single Atom Co-Catalysts in Photocatalytic H2 Generation - Wang, Yue; Qin, Shanshan; Denisov, Nikita; Kim, Hyesung; Bad'ura, Zdeněk; Sarma, Bidyut Bikash; Schmuki, Patrik (Advanced Materials, 2023)
In recent years, the use of single atoms (SAs) has become of a rapidly increasing significance in photocatalytic H2 generation; here SA noble metals (mainly Pt SAs) can act as highly effective co-catalysts. The classic strategy to decorate oxide semiconductor surfaces with maximally dispersed SAs relies on “strong electrostatic adsorption” (SEA) of suitable noble metal complexes. In the case of TiO2 – the classic benchmark photocatalyst – SEA calls for adsorption of cationic Pt complexes such as [(NH3)4Pt]2+ which then are thermally reacted to surface-bound SAs. While SEA is widely used in literature, in the present work it is shown by a direct comparison that reactive attachment based on the reductive anchoring of SAs, e.g., from hexachloroplatinic(IV) acid (H2PtCl6) leads directly to SAs in a configuration with a significantly higher specific activity than SAs deposited with SEA – and this at a significantly lower Pt loading and without any thermal post-deposition treatments. Overall, the work demonstrates that the reactive deposition strategy is superior to the classic SEA concept as it provides a direct electronically well-connected SA-anchoring and thus leads to highly active single-atom sites in photocatalysis.
CRIS-Team Scopus Importer:2023-08-18
Keywords: highly reactive single-atom deposition; photocatalytic H; Pt co-catalysts; sputtered anatase layers

Reliable identification of the complex or superlattice nature of intrinsic and extrinsic stacking faults in the L12 phase by high-resolution imaging - Karpstein, Nicolas; Lenz, Malte; Bezold, Alexander; Wu, Mingjian; Neumeier, Steffen; Spiecker, Erdmann (Acta Materialia, 2023)
Planar defect-based deformation mechanisms are becoming increasingly important for understanding and tuning the mechanical properties of superalloys. Typically, to elucidate such deformation mechanisms, the type of planar defect is determined by conventional transmission electron microscopy or by high-resolution imaging along 〈110〉 crystallographic directions. However, an unambiguous identification of the complex or non-complex nature of intrinsic and extrinsic stacking faults in the L12 phase may not be possible by analyzing only one projection. To overcome this limitation, we present a straightforward approach to identify the superlattice or complex character of intrinsic and extrinsic faults in the L12 structure in high-resolution scanning transmission electron microscopy by tilting to a different zone axis and examining the shift of superlattice planes. Using this approach, two key aspects of the Kolbe mechanism for the formation of superlattice extrinsic stacking faults are verified for the first time: the presence of a complex intrinsic fault segment at the leading end and the occurrence of re-ordering.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Creep; Dislocation; Electron microscopy; Planar defects; Superalloy

Segregation-induced strength anomalies in complex single-crystalline superalloys - Bezold, Andreas; Vollhüter, Jan; Karpstein, Nicolas; Lenz, Malte; Subramanyam, Aparna P.A.; Zenk, Christopher; Hammerschmidt, Thomas; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Communications Materials, 2024)
Pushing the maximum service temperature of aircraft engines and industrial gas turbines is the major pathway to improve their energy efficiency and reduce CO2 emissions. This maximum is mostly limited by the temperature capability of key-component materials, including superalloys. In this alloy class, segregation of elements facilitates plastic deformation and is generally considered to cause softening during high-temperature deformation. Here, we show that segregation-assisted processes can also lead to strengthening and induce an anomalous increase of the yield strength. Atomic-resolution transmission electron microscopy and density functional theory calculations reveal a segregation-assisted dissociation process of dislocations at precipitate-matrix interfaces in combination with atomic-scale reordering processes. These processes lead to an inhibition of athermal deformation mechanisms and a transition to stacking fault shearing, which causes the strengthening effect. Unraveling these elementary mechanisms might guide a mechanism-based alloy design of future superalloys with enhanced high-temperature capabilities.
CRIS-Team Scopus Importer:2024-02-02

Single Atoms in Photocatalysis: Low Loading Is Good Enough! - Qin, Shanshan; Will, Johannes; Kim, Hyesung; Denisov, Nikita; Carl, Simon; Spiecker, Erdmann; Schmuki, Patrik (ACS Energy Letters, 2023)
We disperse Pt single atoms (SAs) with different loading densities on anatase TiO2 thin films and evaluate the photocatalytic H2 generation as a function of the incident light intensity. We show that under common illumination intensities (such as terrestrial solar illumination), a minuscule Pt SA loading of ∼105 atoms μm-2 (surface Pt content ∼0.1 at.%) is sufficient to achieve a maximized H2 production rate. This results in a maximum turnover frequency at a single Pt atom site of ∼300 H2 molecules s-1. For a vast majority of illumination conditions and a suitable surface configuration, it is not the density of co-catalytic sites that is rate-determining (a high loading is not needed!), but the charge carrier generation (and flux of photoelectrons to the co-catalytic centers) determines the overall reaction rate. This is in stark contrast to SA catalysis of classic chemical reactions where generally a maximum loading of reactive SA delivers a maximum activity.
CRIS-Team Scopus Importer:2023-02-10

Solution-Growth Liquid-Phase Epitaxy of CsPbBr3 on NaCl by Optimizing the Substrate Dissolution - Elia, Jack; Levchuk, Ievgen; Hou, Yi; Matt, Gebhard; These, Albert; Zhao, Yicheng; Zhang, Jiyun; Forberich, Karen; Osvet, Andres; Götz, Klaus; Prihoda, Annemarie; Wu, Mingjian; et al. (Journal of Physical Chemistry C, 2023)
Since the earliest days of liquid-phase epitaxy (LPE) research, substrate stability has been a prerequisite for investigating nucleation and epitaxial growth. For flux- and melt-growth LPE, soluble substrates have always been viewed as problematic and difficult. However, solution-growth LPE transforms this disadvantage into a benefit by facilitating the creation of graded interfaces. In this study, we investigated the nucleation and growth of solution-grown LPE in the evaporation mode of soluble CsPbBr3 on freshly cleaved NaCl single-crystal substrates. Only two of the four main types of CsPbBr3 crystallization observed are epitaxial. The microscopic observation of composition gradients at the interface of CsPbBr3 grains and substrates reveals a promising opportunity to manipulate the lattice constant at the interface by simply controlling the temperature and concentration.
CRIS-Team Scopus Importer:2023-12-08

Solving complex nanostructures with ptychographic atomic electron tomography - Pelz, Philipp; Griffin, Sinéad M.; Stonemeyer, Scott; Popple, Derek; DeVyldere, Hannah; Ercius, Peter; Zettl, Alex; Scott, Mary C.; Ophus, Colin (Nature Communications, 2023)
Transmission electron microscopy (TEM) is essential for determining atomic scale structures in structural biology and materials science. In structural biology, three-dimensional structures of proteins are routinely determined from thousands of identical particles using phase-contrast TEM. In materials science, three-dimensional atomic structures of complex nanomaterials have been determined using atomic electron tomography (AET). However, neither of these methods can determine the three-dimensional atomic structure of heterogeneous nanomaterials containing light elements. Here, we perform ptychographic electron tomography from 34.5 million diffraction patterns to reconstruct an atomic resolution tilt series of a double wall-carbon nanotube (DW-CNT) encapsulating a complex ZrTe sandwich structure. Class averaging the resulting tilt series images and subpixel localization of the atomic peaks reveals a Zr11Te50 structure containing a previously unobserved ZrTe2 phase in the core. The experimental realization of atomic resolution ptychographic electron tomography will allow for the structural determination of a wide range of beam-sensitive nanomaterials containing light elements.
CRIS-Team Scopus Importer:2023-12-15

Squeezing the Threshold of Metal-Halide Perovskite Micro-Crystal Lasers Grown by Solution Epitaxy - Zhou, Shuyu; Rehm, Viktor; Afify, Hany A.; Feng, Yufei; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Peng, Zijian; These, Albert; Barabash, Anastasia; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2024)
Metal halide perovskite semiconductors have demonstrated remarkable progress not only in photovoltaics and X-ray detection but also in laser technologies. Particularly appealing is the simplicity with which micro-crystallites can be epitaxially grown, thereby forming micro-resonators suitable for lasing. Here, the laser threshold is optimized by selecting excitation laser parameters and by improving material quality. The latter process is conducted for formamidinium lead tribromide, emitting in the green spectral range. Depending on the growth method and parameters, the sizes of the micro-resonators can be tuned between ≈3 and 23 micrometers. Under laser excitation systematically lower thresholds are observed for micro-resonators in the 4–7 micrometer size range, than for larger ones, irrespective of growth method. Among three optimized growth methods, epitaxial growth via antisolvent vapor-assisted crystallization exhibits the smallest threshold powers, indicating the highest material quality. This conclusion is supported by hyperspectral microscopic luminescence imaging and by transient photoluminescence. The best laser structures exhibit record threshold powers for epitaxially grown perovskites, indicating that the selected antisolvent vapor epitaxial growth holds great promises also for other perovskite materials.
CRIS-Team Scopus Importer:2024-05-10
Keywords: FAPbBr; lasing; micro-resonators; perovskites; solution epitaxy

Strain Rate-Dependent Anomalous Work Hardening of a Single-Crystalline CoNi-Base Superalloy - Vollhüter, Jan; Bezold, Andreas; Karpstein, N.; Köbrich, Manuel; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
The deformation mechanisms operating in superalloys depend on different parameters such as composition, temperature and deformation rate. So far, the transition from shearing by APB-coupled dislocations to shearing under the formation of stacking faults has been studied exclusively as a function of temperature but not as a function of the strain rate. Therefore, interrupted compression tests with strain rates between 10–3 s−1 and 10–5 s−1 were performed on the single-crystalline CoNi-base superalloy ERBOCo-4 at a temperature of 850 °C. The evolution of the defect structures has been analyzed by conventional transmission electron microscopy. A change of the deformation mechanism from APB-coupled dislocation shearing to stacking fault shearing is found to depend on the strain rate. At lower strain rates, an increased stacking fault density is associated with a higher yield strength and higher work hardening rates at the early stages of plastic deformation due to a very high stacking fault density. After approximately 2.0 pct plastic strain, the stress reaches a plateau and decreases subsequently, which is associated with the formation and thickening of twins as shown by high-resolution scanning transmission electron microscopy. At higher strain rates, the work hardening rate is significantly lower in the early deformation stage. The role of segregation to planar defects and the influence of local phase transformations (LPT) at SESFs is further discussed in reference to the influence of the strain rate. The segregation of W as an η stabilizing element is found to be crucial for the formation of a local phase transformation in ERBOCo-4. At higher strain rates the phase transformation is hindered by insufficient W segregation, resulting in a higher twin density.
CRIS-Team Scopus Importer:2023-02-24

Structural Evolution of GaOx-Shell and Intermetallic Phases in Ga-Pt Supported Catalytically Active Liquid Metal Solutions - Carl, Simon; Will, Johannes; Madubuko, Nnamdi; Götz, Alexander; Przybilla, Thomas; Wu, Mingjian; Raman, Narayanan; Wirth, Janis; Taccardi, Nicola; Apeleo Zubiri, Benjamin; Haumann, Marco; Wasserscheid, Peter; et al. (Journal of Physical Chemistry Letters, 2024)
We present a comprehensive scale-bridging characterization approach for supported catalytically active liquid metal solutions (SCALMS) which combines lab-based X-ray microscopy, nano X-ray computed tomography (nano-CT), and correlative analytical transmission electron microscopy. SCALMS catalysts consist of low-melting alloy particles and have demonstrated high catalytic activity, selectivity, and long-term stability in propane dehydrogenation (PDH). We established an identical-location nano-CT workflow which allows us to reveal site-specific changes of Ga-Pt SCALMS before and after PDH. These observations are complemented by analytical transmission electron microscopy investigations providing information on the structure, chemical composition, and phase distribution of individual SCALMS particles. Key findings of this combined microscopic approach include (i) structural evolution of the SCALMS particles’ GaOx shell, (ii) Pt segregation toward the oxide shell leading to the formation of Ga-Pt intermetallic phases, and (iii) cracking of the oxide shell accompanied by the release of liquid Ga-Pt toward the porous support.
CRIS-Team Scopus Importer:2024-05-10

Supraparticles on beads for supported catalytically active liquid metal solutions - the SCALMS suprabead concept - Zimmermann, Thomas; Madubuko, Nnamdi; Groppe, Philipp; Raczka, Theodor; Dünninger, Nils; Taccardi, Nicola; Carl, Simon; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Wasserscheid, Peter; Mandel, Karl; Haumann, Marco; et al. (Materials Horizons, 2023)
A novel GaPt-based supported catalytically active liquid metal solution (SCALMS) material is developed by exploiting the suprabead concept: Supraparticles, i.e. micrometer-sized particles composed of nanoparticles assembled by spray-drying, are bonded to millimeter-sized beads. The suprabeads combine macroscale size with catalytic properties of nanoscale GaPt particles entrapped in their silica framework.
Created from Fastlane, Scopus look-up

Synergistic Combination of Reductive Covalent Functionalization and Atomic Layer Deposition—Towards Spatially Defined Graphene-Organic-Inorganic Heterostructures - Liu, Xin; Yang, Bowen; Zhou, Xin; Wu, Mingjian; Spiecker, Erdmann; Bachmann, Julien; Hauke, Frank; Hirsch, Andreas; Wei, Tao (Angewandte Chemie International Edition, 2023)
Three-dimensionally (3D) well-ordered and highly integrated graphene hybrid architectures are considered to be next-generation multifunctional graphene materials but still remain elusive. Here, we report the first realization of unprecedented 3D-patterned graphene nano-ensembles composed of a graphene monolayer, a tailor-made structured organophenyl layer, and three metal oxide films, providing the first example of such a hybrid nano-architecture. These spatially resolved and hierarchically structured quinary hybrids are generated via a two-dimensional (2D)-functionalization-mediated atomic layer deposition growth process, involving an initial lateral molecular programming of the graphene lattice via lithography-assisted 2D functionalization and a subsequent stepwise molecular assembly in these regions in the z-direction. Our breakthrough lays the foundation for the construction of emerging 3D-patterned graphene heterostructures.
CRIS-Team Scopus Importer:2023-10-27
Keywords: 3D Patterning; Atomic Layer Deposition; Graphene Chemistry; Heteroarchitectures; Molecular Assembly

Tailoring doped organic nanoparticles as selective hole transporters for printed non-fullerene organic solar cells - Xu, Junyi; Späth, Andreas; Gruber, Wolfgang; Barabash, Anastasia; Stadler, Philipp; Gubanov, Kirill; Wu, Mingjian; Forberich, Karen; Spiecker, Erdmann; Fink, Rainer H.; Unruh, Tobias; McCulloch, Iain; et al. (Nano Energy, 2023)
Keywords: Inverted structure; Organic nanoparticle; Doping; Organic solar cell; Solution-processed hole transporting layer

Tailoring the Acidity of Liquid Media with Ionizing Radiation: Rethinking the Acid-Base Correlation beyond pH - Fritsch, Birk; Körner, Andreas; Couasnon, Thaïs; Blukis, Roberts; Taherkhani, Mehran; Benning, Liane G.; Jank, Michael; Spiecker, Erdmann; Hutzler, Andreas (Journal of Physical Chemistry Letters, 2023)
Advanced in situ techniques based on electrons and X-rays are increasingly used to gain insights into fundamental processes in liquids. However, probing liquid samples with ionizing radiation changes the solution chemistry under observation. In this work, we show that a radiation-induced decrease in pH does not necessarily correlate to an increase in acidity of aqueous solutions. Thus, pH does not capture the acidity under irradiation. Using kinetic modeling of radiation chemistry, we introduce alternative measures of acidity (radiolytic acidity π* and radiolytic ion product KW*), that account for radiation-induced alterations of both H+ and OH- concentration. Moreover, we demonstrate that adding pH-neutral solutes such as LiCl, LiBr, or LiNO3 can trigger a significant change in π*. This provides a huge parameter space to tailor the acidity for in situ experiments involving ionizing radiation, as present in synchrotron facilities or during liquid-phase electron microscopy.
CRIS-Team Scopus Importer:2023-06-30

Tailoring the Dimensionality of 2D/3D Heterojunctions for Inverted Perovskite Solar Cells - Li, Chaohui; Zhang, Kaicheng; Maiti, Santanu; Peng, Zijian; Tian, Jingjing; Park, Hyoungwon; Byun, Jiwon; Xie, Zhiqiang; Dong, Lirong; Qiu, Shudi; Bornschlegl, Andreas; Liu, Chao; et al. (ACS Energy Letters, 2024)
Interface engineering is crucial to achieving stable perovskite photovoltaic devices. A versatile approach is developed to tailor interface properties via integrating co-assembled monolayers (co-SAMs) at the p-type buried interface and by capping a two-dimensional (2D) perovskite layer at the n-type upper interface with vacuum quenching. Optimized co-SAMs promote the coverage of the hole transport layer, significantly reducing the incidence of leakage currents. Based on this foundation, we develop damp-heat-stable perovskite solar cells by precisely tailoring the fragments of 2D perovskite layers through vacuum annealing with phenethylammonium iodide. An impressive open-circuit voltage of 1.216 V is achieved, corresponding to 92% of the value determined by the detailed-balance limit, along with a power conversion efficiency of 23.68%. Ultimately, integrating co-SAMs and the vacuum-assisted annealing fabricated devices maintain 96% and 80% of initial efficiencies after 1200 and 500 h of tracking at a maximum power point under 55 and 85 °C, respectively.
CRIS-Team Scopus Importer:2024-02-23

Tailoring the Reaction Pathway for Control of Size and Composition of Silver-Gold Alloy Nanoparticles - Traore, Nabi; Berthold, Michelle; Hartmann, Lukas; Schmul, Patricia; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Journal of Physical Chemistry C, 2024)
In this work, we independently tune both the particle size and the chemical composition of bimetallic silver−gold alloy nanoparticles (NPs) by carefully controlling the reaction pathway. NP synthesis involves control of the supersaturation profile in time and space. For the reaction-controlled case, this supersaturation profile is determined by a network of reactions leading to the buildup of the monomer concentration. Using a variety of characterization tools, we show how the process conditions influence the coupled reactions in the complex formation mechanism of Ag−Au alloy NPs. Applying a simple mass balance allows for the independent control of size and chemical composition of these NPs, yielding particles with constant composition and varying size in the range of 20 to 40 nm. A series of constant sizes and varying chemical compositions in the range of 10% to 100% molar gold content is also possible. Our new methodology shows an example of how reaction networks can be tailored to achieve targeted NP properties and paves the way for better control in the synthesis of multicomponent NPs.<br

Targeted color design of silver-gold alloy nanoparticles - Traore, Nabi; Spruck, Christina; Uihlein, Andrian; Pflug, Lukas; Peukert, Wolfgang (Nanoscale Advances, 2023)
This research article focuses on the targeted color design of silver-gold alloy nanoparticles (NPs), employing a multivariate optimization approach. NP synthesis involves interconnected process parameters, making independent variation challenging. Data-based property-process relationships are established to optimize optical properties effectively. We define a color target, employ a green chemical co-reduction method at room temperature and optimize process parameters accordingly. The CIEL*a*b* color space (Commission Internationale de l'Éclairage - International Commission on Illumination) and Euclidean distances facilitate accurate color matching to establish the property-process relationship. Concurrently, theoretical Mie calculations explore the structure-property relationship across particle sizes, concentrations, and molar gold contents. The theoretically optimal structure agrees very well with experimental particle structures at the property-process relationship's optimum. The data-driven property-process relationship provides valuable insights into the formation mechanism of a complex particle system, sheds light on the role of relevant process parameters and allows to evaluate the practically available property space. Model validation beyond the original grid demonstrates its robustness, yielding colors close to the target. Additionally, Design of Experiments (DoE) methods reduce experimental work by threefold with slight accuracy trade-offs. Our novel methodology for targeted color design demonstrates how data-based methods can be utilized alongside structure-property relationships to unravel property-process relationships in the design of complex nanoparticle systems and paves the way for future developments in targeted property design.
CRIS-Team Scopus Importer:2023-12-22

The challenge with high permittivity acceptors in organic solar cells: a case study with Y-series derivatives - Fürk, Peter; Mallick, Suman; Rath, Thomas; Reinfelds, Matiss; Wu, Mingjian; Spiecker, Erdmann; Simic, Nikola; Haberfehlner, Georg; Kothleitner, Gerald; Ressel, Barbara; Holler, Sarah; Schaubeder, Jana B.; et al. (Journal of Materials Chemistry C, 2023)
Y-series acceptors have brought a paradigm shift in terms of power conversion efficiencies of organic solar cells in the last few years. Despite their high performance, these acceptors still exhibit substantial energy loss, stemming from their low-permittivity nature. To tackle the energy loss situation, we prepared modified Y-series acceptors with improved permittivities via an alternative synthetic route. The route yields a thienothiophene block, which can be easily functionalized further on. That way, two new acceptors (Y-thio-EG and Y-pyr-EG) were synthesized with permittivity-improving glycol side chains in the central pyrrol and outer thiophene substitution site. Both acceptors exhibit a significantly increased relative permittivity (4.73 and 5.24, respectively), compared to Y6 (2.39). When employed in binary bulk heterojunction solar cells with PM6 as polymer, however, both acceptors only reach efficiencies of 8.2% (Y-thio-EG) and 5.3% (Y-pyr-EG). We show by extensive morphology investigation (atomic force microscopy, transmission electron microscopy and X-ray scattering) that the glycol modification and side chain positioning have a strong influence on the crystallization behaviour of these acceptors. A thorough comparison of the acceptors blended with PM6 to PM6:Y6 absorber layers showed that differences in crystallinity and aggregation behaviour are present. However, the degree of the morphological change is likely not the main reason for the large efficiency drops of the solar cells. We hypothesize that the combination of an apolar donor with polar, glycol-modified acceptors yields a much more complex situation in the bulk heterojunction absorber layer, where further effects - such as interface dipole formation, energy level broadening and increased interface-state assisted recombination - are also expected to be highly relevant. Eventually we propose strategies to circumvent these issues in future permittivity modification research.
Created from Fastlane, Scopus look-up

Ultra-low resistance Au-free V/Al/Ti/TiN ohmic contacts for AlGaN/GaN HEMTs - Garbe, Valentin; Seidel, Sarah; Schmid, Alexander; Bläß, Ulrich; Meissner, Elke; Heitmann, Johannes (Applied Physics Letters, 2023)
We report on the electrical and microstructural characterization of an Au-free V/Al/Ti/TiN ohmic contact for AlGaN/GaN heterostructures. Ultra-low contact resistance and specific contact resistivity of Rc < 0.1 Ω mm and ρc < 2.4 × 10−7 Ω cm2 have been achieved with very low RMS surface roughness. This was accomplished at a comparably low annealing temperature of 800 °C and without applying any contact recess, regrowth, or implantation process. High electron mobility transistors were fabricated and a comparison of the electrical performance with state-of-the-art Ti/Al/Ti/TiN and Ti/Al/Ni/Au contacts was made. The contact formation mechanism is discussed on the basis of microstructural features.
CRIS-Team Scopus Importer:2023-12-01

Using a fast hybrid pixel detector for dose-efficient diffraction imaging beam-sensitive organic molecular thin films - Wu, Mingjian; Stroppa, Daniel G.; Pelz, Philipp; Spiecker, Erdmann (JPhys Materials, 2023)
We discuss the benefits and showcase the applications of using a fast, hybrid-pixel detector (HPD) for 4D-STEM experiments and emphasize that in diffraction imaging the structure of molecular nano-crystallites in organic solar cell thin films with a dose-efficient modality 4D-scanning confocal electron diffraction (4D-SCED). With 4D-SCED, spot diffraction patterns form from an interaction area of a few nm while the electron beam rasters over the sample, resulting in high dose effectiveness yet highly demanding on the detector in frame speed, sensitivity, and single-pixel count rate. We compare the datasets acquired with 4D-SCED using a fast HPD with those using state-of-the-art complementary metal-oxide-semiconductor (CMOS) cameras to map the in-plane orientation of π-stacking nano-crystallites of small molecule DRCN5T in a blend of DRCN5T: PC71BM after solvent vapor annealing. The high-speed CMOS camera, using a scintillator optimized for low doses, showed impressive results for electron sensitivity and low noise. However, the limited speed restricted practical experimental conditions and caused unintended damage to small and weak nano-crystallites. The fast HPD, with a speed three orders of magnitude higher, allows a much higher probe current yet a lower total dose on the sample, and more scan points cover a large field of view in less time. A lot more faint diffraction signals that correspond to just a few electron events are detected. The improved performance of direct electron detectors opens more possibilities to enhance the characterization of beam-sensitive materials using 4D-STEM techniques.
CRIS-Team Scopus Importer:2023-10-20
Keywords: 4D-STEM; electron detector; electron microscopy; molecular crystal; organic materials

Using OpenBIS as Virtual Research Environment: An ELN-LIMS Open-Source Database Tool as a Framework within the CRC 1411 Design of Particulate Products - Plass, Fabian; Englisch, Silvan; Apeleo Zubiri, Benjamin; Pflug, Lukas; Spiecker, Erdmann; Stingl, Michael (Data Science Journal, 2023)
The digital transformation and consequent use of new digital technologies not only have a substantial impact on society and companies, but also on science. Analog documentation as we have known it for centuries will eventually be replaced by intelligent and FAIR (Findable, Accessible, Interoperable, and Reusable) systems. In addition to the actual research data and results, metadata now plays an important role not only for individual, independently existing projects, but for future scientific use and interdisciplinary research groups and disciplines as well. The solution presented here, consisting of an electronic laboratory notebook and laboratory information management system (ELN-LIMS) based on the openBIS (open Biology Information System) environment, offers interesting features and advantages, especially for interdisciplinary work. The Collaborative Research Centre (CRC) 1411 ‘Design of Particulate Products’ of the German Research Foundation is characterized by the cooperation of different working groups of synthesis, characterization, and simulation, and therefore serves as a model environment to present the implementation of openBIS. OpenBIS, as an open source ELN-LIMS solution following FAIR principles, provides a common set of general entries with the possibility of sharing and linking (meta-)data to improve the scientific exchange between all users.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Databases; ELN-LIMS; Interdisciplinary work; Open Science; Research data management